Fluorine-containing ether compound, lubricant for magnetic recording medium, and magnetic recording medium
A fluorine-containing ether compound with a specific molecular structure addresses the challenges of magnetic head attachment and lubricant spin-off by enhancing adhesion and reducing peeling in magnetic recording media, ensuring stable operation under high-speed conditions.
Patent Information
- Application Number
- CN202180012154.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-07
- Filing Date
- 2021-02-02
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-02-02
AI Technical Summary
Magnetic recording media face challenges in increasing recording density due to issues such as magnetic head attachment, lubricant spin-off, and peeling of the lubricating layer, particularly with reduced flying height and film thickness.
A fluorine-containing ether compound with a specific molecular structure, represented by formula (1), is used to form a lubricating layer that enhances adhesion to the protective layer, reducing sticking and peeling, even at low molecular weights.
The fluorine-containing ether compound forms a lubricating layer with excellent adhesion to the protective layer, suppressing sticking and peeling, and is resistant to scattering and evaporation during high-speed rotation.
Smart Images

Figure CN115038685B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a fluorine-containing ether compound suitable for use as a lubricant for a magnetic recording medium, a lubricant for a magnetic recording medium containing the fluorine-containing ether compound, and a magnetic recording medium.
[0002] This application claims priority based on Japanese Patent Application No. 2020-020180 filed in Japan on February 7, 2020, the contents of which are incorporated herein by reference. Background Art
[0003] In recent years, as the amount of information processed via the Internet has increased dramatically, the development of recording media for storing this information has attracted much attention. In particular, magnetic recording media, which is a type of recording medium, is expected to be a receiver of increased information because of its low cost and high capacity.
[0004] In order to ensure the durability and reliability of magnetic recording media, a protective layer and a lubricating layer are provided on the magnetic layer (magnetic recording layer) formed on the substrate. In particular, the lubricating layer disposed on the outermost surface is required to have various properties such as long-term stability, chemical resistance (prevention of contamination by siloxane, etc.), wear resistance, and heat resistance.
[0005] As lubricants for magnetic recording media, lubricants containing compounds having polar groups such as hydroxyl groups at the ends of fluorine-based polymers having a repeating structure containing CF 2 have been proposed (for example, see Patent Documents 1 to 7).
[0006] Specifically, Patent Document 1 discloses a compound having a plurality of hydroxyl groups at both terminal portions of a fluorine-based polymer, which are arranged such that the shortest distance between the hydroxyl groups is 3 atoms or more.
[0007] Patent Document 2 discloses a fluoropolyether compound having an aromatic group at one terminal of a fluorine-based polymer and a hydroxyl group at the other terminal.
[0008] Patent Document 3 discloses a compound having a perfluoropolyether main chain and having an aromatic group and a hydroxyl group at the terminal of the molecule, wherein the aromatic group and the hydroxyl group are bonded to different carbon atoms, respectively.
[0009] Patent Document 4 discloses a fluorine-containing ether compound having a perfluoropolyether chain. A terminal group containing an organic group having at least one double bond or triple bond is arranged at one end of the perfluoropolyether chain via a divalent linking group bonded via etheric oxygen. A terminal group is arranged at the other end of the perfluoropolyether chain, the terminal group containing two or three polar groups, each polar group is bonded to a different carbon atom, and the carbon atoms bonded to the polar groups are bonded to each other via a linking group containing a carbon atom to which the polar groups are not bonded.
[0010] Patent Document 5 discloses a fluorinated ether compound having a perfluoropolyether chain. As the terminal groups at both ends of the fluorinated ether compound, any one of an alkyl group which may have a substituent, an organic group having at least one double bond or triple bond, and a hydrogen atom is disposed. In addition, a linking group containing a hydroxyl group is disposed between the perfluoropolyether chain and the terminal groups at both ends.
[0011] Patent Document 6 discloses a fluorine-containing ether compound having a perfluoropolyether chain. An alkyl group which may have a substituent is disposed at one end of the perfluoropolyether chain via a divalent linking group. A terminal group is disposed at the other end of the perfluoropolyether chain, and the terminal group includes two or three polar groups, each of which is bonded to a different carbon atom, and the carbon atoms bonded to the polar groups are bonded to each other via a linking group including a carbon atom to which the polar groups are not bonded.
[0012] Patent Document 7 discloses a fluorinated ether compound having a perfluoropolyether chain. As at least one of the terminal groups of the fluorinated ether compound, a group in which one or more hydrogen atoms of an organic group having 1 to 8 carbon atoms are replaced by a cyano group is arranged. In addition, a divalent linking group having a polar group is arranged between the perfluoropolyether chain and the terminal group.
[0013] Prior art literature
[0014] Patent Literature
[0015] Patent Document 1: Japanese Patent No. 4632144
[0016] Patent Document 2: Japanese Patent No. 5909837
[0017] Patent Document 3: Japanese Patent No. 5465454
[0018] Patent Document 4: International Publication No. 2017 / 154403
[0019] Patent Document 5: International Publication No. 2019 / 054148
[0020] Patent Document 6: International Publication No. 2019 / 049585
[0021] Patent Document 7: International Publication No. 2019 / 039200 Summary of the invention
[0022] Problems to be solved by the invention
[0023] In order to increase the recording density of magnetic recording media and thus increase the capacity, it is necessary to reduce the magnetic pitch, which is the distance between the magnetic head and the magnetic layer of the magnetic recording medium. As a method of reducing the magnetic pitch, it is possible to reduce the flying height of the magnetic head or to reduce the film thickness of the lubricating layer.
[0024] However, if the flying height of the magnetic head is reduced, the fluorine-containing ether compound in the lubricating layer is likely to be attached to the magnetic head as a foreign matter (stain) and pick up.
[0025] In recent years, the rotation speed of magnetic recording media has increased. As a result, the lubricating layer is prone to spin-off. Spin-off is a phenomenon in which the lubricant is scattered or evaporated due to the centrifugal force and heat generated by the rotation of the magnetic recording medium.
[0026] The thickness of the lubricating layer can be reduced by reducing the average molecular weight of the lubricant, but in this case, peeling is likely to occur.
[0027] The present invention is proposed in view of the above situation, and its object is to provide a fluorinated ether compound that can form a lubricating layer that is not affected by the average molecular weight of the fluorinated ether compound in the lubricant and is not easily sticky or detached, and can be suitably used as a material for a lubricant for a magnetic recording medium.
[0028] Another object of the present invention is to provide a lubricant for a magnetic recording medium comprising the fluorinated ether compound of the present invention.
[0029] Another object of the present invention is to provide a magnetic recording medium having a lubricating layer containing the fluorinated ether compound of the present invention.
[0030] Means for solving problems
[0031] The present inventors have conducted intensive studies to solve the above-mentioned problems.
[0032] As a result, the inventors found that the use of a lubricant for a magnetic recording medium containing a fluorinated ether compound having a specific molecular structure can form a lubricating layer that has good adhesion to the protective layer and can suppress sticking and peeling even when the molecular weight is low, thereby arriving at the present invention.
[0033] That is, the present invention relates to the following matters.
[0034] [1] A fluorine-containing ether compound characterized by being represented by the following formula (1).
[0035] R 1 -(O(CH2) a ) b -[A]-[B]-O-CH2-R 2 -CH2-R 3 (1)
[0036] (In formula (1), R 1is any one of an alkyl group which may have a substituent and an organic group having at least one double bond or triple bond. a is an integer of 2 to 4, and b is 0 or 1. [A] is represented by the following formula (2). c in formula (2) is 1 or 2. [B] is represented by the following formula (3). d in formula (3) is 0 or 1, and e is an integer of 2 to 4. The sum of the values of c in formula (2) and d in formula (3) is 2. R 2 R is a perfluoropolyether chain. 3 It is represented by the following formula (4). In the formula (4), f is an integer of 2 to 5.
[0037]
[0038] [2] The fluorinated ether compound according to [1], which has a number average molecular weight in the range of 1,000 to 2,300.
[0039] [3] The fluorinated ether compound according to [1] or [2], wherein R in the formula (1) 1 It is an alkyl group having 1 to 6 carbon atoms.
[0040] [4] The fluorinated ether compound according to [1] or [2], wherein R in the formula (1) 1 is an alkyl group having 1 to 6 carbon atoms and having a substituent,
[0041] The above substituent is a fluoro group or a cyano group.
[0042] [5] The fluorinated ether compound according to [1] or [2], wherein R in the formula (1) 1 It is any one of an organic group having 6 to 12 carbon atoms having an aromatic hydrocarbon, an organic group having 3 to 10 carbon atoms having an aromatic heterocycle, an alkenyl group having 2 to 8 carbon atoms, and an alkynyl group having 3 to 8 carbon atoms.
[0043] [6] The fluorinated ether compound according to [1] or [2], wherein R in the formula (1) 1 It is one group selected from methyl, ethyl, n-propyl, isopropyl, 2,2,2-trifluoroethyl, 2,2,3,3,3-pentafluoropropyl, 2,2,2,2,2,2-hexafluoroisopropyl, 2-cyanoethyl, 3-cyanopropyl, 4-cyanobutyl, phenyl, methoxyphenyl, cyanophenyl, phenethyl, thienylethyl, N-methylpyrazolylmethyl, allyl, 3-butenyl, 4-pentenyl, propargyl, 3-butynyl, and 4-pentynyl.
[0044] [7] The fluorinated ether compound according to any one of [1] to [6], wherein R in the formula (1) 2 It is any one of the following formulas (5) to (8).
[0045] -CF2O-(CF2CF2O)g -(CF2O) h -CF2- (5)
[0046] (In formula (5), g and h are average polymerization degrees, g represents 3 to 8, and h represents 3 to 8.)
[0047] -CF2O-(CF2CF2O) i -CF2- (6)
[0048] (i in formula (6) is an average degree of polymerization and represents 5 to 13.)
[0049] -CF2CF2O-(CF2CF2CF2O) j -CF2CF2- (7)
[0050] (j in formula (7) is the average degree of polymerization and represents 3 to 8.)
[0051] -CF(CF3)-(OCF(CF3)CF2) k -OCF(CF3)- (8)
[0052] (k in formula (8) is an average degree of polymerization and represents 3 to 8.)
[0053] [8] The fluorinated ether compound according to [1], wherein the compound represented by the formula (1) is any one of the compounds represented by the following formulae (A1) to (A3), (B1) to (B3), (L1), and (M1).
[0054]
[0055] (In formula (A1), ma1 and na1 are average polymerization degrees, ma1 represents 3 to 8, and na1 represents 3 to 8.)
[0056] (In formula (A2), na2 is the average degree of polymerization and represents 5 to 13.)
[0057] (In formula (A3), na3 is the average degree of polymerization and represents 3 to 8.)
[0058] (In formula (B1), mb1 and nb1 are average polymerization degrees, mb1 represents 3 to 8, and nb1 represents 3 to 8.)
[0059] (In formula (B2), nb2 is the average degree of polymerization and represents 5 to 13.)
[0060] (In formula (B3), nb3 is the average degree of polymerization and represents 3 to 8.)
[0061] (In formula (L1), ml1 and nl1 are average polymerization degrees, ml1 represents 3 to 8, and nl1 represents 3 to 8.)
[0062] (In formula (M1), mm1 and nm1 are average polymerization degrees, mm1 represents 3 to 8, and nm1 represents 3 to 8.)
[0063] [9] A lubricant for a magnetic recording medium, comprising the fluorine-containing ether compound according to any one of [1] to [8].
[0064]
[10] A magnetic recording medium, characterized in that at least a magnetic layer, a protective layer and a lubricating layer are provided in this order on a substrate, wherein the lubricating layer contains the fluorine-containing ether compound described in any one of [1] to [8].
[0065]
[11] The magnetic recording medium according to
[10] , wherein the average film thickness of the lubricating layer is 0.5 nm to 2.0 nm.
[0066] Effects of the Invention
[0067] The fluorine-containing ether compound of the present invention is a compound represented by the above formula (1), and is suitable as a material for a lubricant for a magnetic recording medium.
[0068] The lubricant for magnetic recording media of the present invention contains the fluorine-containing ether compound of the present invention, so that a lubricating layer having good adhesion to the protective layer and capable of suppressing sticking and falling off can be formed without being affected by the average molecular weight of the fluorine-containing ether compound in the lubricant.
[0069] The magnetic recording medium of the present invention has a lubricating layer that has good adhesion to the protective layer and can suppress sticking and peeling. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 This is a schematic cross-sectional view showing one embodiment of the magnetic recording medium of the present invention. DETAILED DESCRIPTION
[0071] In order to solve the above-mentioned problems, the present inventors paid attention to the relationship between the molecular structure of the fluorine-containing ether compound contained in the lubricating layer and the protective layer, and conducted intensive studies as shown below.
[0072] The molecular structure of the fluorine-containing ether compound contained in the lubricating layer has a great influence on the film thickness and adhesion characteristics of the lubricating layer.
[0073] Conventionally, in order to obtain a lubricating layer with good adhesion to the protective layer, a perfluoropolyether compound containing a hydroxyl group in the molecule (hereinafter sometimes referred to as a "PFPE compound") has been used as a lubricant. However, even a lubricating layer containing a PFPE compound having a plurality of hydroxyl groups in the molecule may not sufficiently adhere to the protective layer.
[0074] The present inventors have conducted intensive studies and found that even if the lubricating layer includes a PFPE compound having multiple hydroxyl groups, sufficient adhesion to the protective layer cannot be achieved unless the hydroxyl groups in the PFPE compound effectively participate in bonding with active sites on the protective layer.
[0075] Furthermore, the inventors have conducted in-depth research and found that if a large amount of hydroxyl groups not involved in the bonding with the active points on the protective layer are present in the PFPE-based compound included in the lubricating layer, there is a tendency as shown below: that is, the lubricant is easily shed due to the scattering / evaporation caused by the centrifugal force and heat during high-speed rotation, or the lubricant is easily attached to the magnetic head as a foreign matter (stain).
[0076] Therefore, the present inventors have conducted repeated studies focusing on the molecular structure of the fluorine-containing ether compound in order to promote the bonding between the plurality of hydroxyl groups in the fluorine-containing ether compound and the active sites on the protective layer, thereby completing the present invention.
[0077] The fluorine-containing ether compound, the lubricant for a magnetic recording medium (hereinafter, sometimes abbreviated as "lubricant"), and the magnetic recording medium of the present invention are described in detail below. It should be noted that the present invention is not limited to the embodiments described below.
[0078] [Fluorinated ether compounds]
[0079] The fluorine-containing ether compound of the present embodiment is represented by the following formula (1).
[0080] R 1 -(O(CH2) a ) b -[A]-[B]-O-CH2-R 2 -CH2-R 3 (1)
[0081] (In formula (1), R 1 is any one of an alkyl group which may have a substituent and an organic group having at least one double bond or triple bond. a is an integer of 2 to 4, and b is 0 or 1. [A] is represented by the following formula (2). c in formula (2) is 1 or 2. [B] is represented by the following formula (3). d in formula (3) is 0 or 1, and e is an integer of 2 to 4. However, the sum of the values of c in formula (2) and d in formula (3) is 2. R2 R is a perfluoropolyether chain. 3 It is represented by the following formula (4). In the formula (4), f is an integer of 2 to 5.
[0082]
[0083] In the fluorine-containing ether compound represented by formula (1), R 1 is a terminal group, and is any one of an alkyl group which may have a substituent and an organic group which has at least one double bond or triple bond. The alkyl group which may have a substituent and the organic group which has at least one double bond or triple bond may also contain any one of an oxygen atom, a sulfur atom and a nitrogen atom.
[0084] R 1 It is an alkyl group having 1 to 6 carbon atoms, or an alkyl group having 1 to 6 carbon atoms having a substituent. Examples of the substituent include a fluoro group and a cyano group. One or more hydrogen atoms of the alkyl group may be substituted. All hydrogen atoms of the alkyl group may be substituted with substituents.
[0085] Furthermore, the alkyl group having 1 to 6 carbon atoms and the alkyl group having 1 to 6 carbon atoms which has a substituent may be linear or branched.
[0086] Examples of the alkyl group having 1 to 6 carbon atoms include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl and structural isomers thereof, and n-hexyl and structural isomers thereof.
[0087] Examples of the alkyl group having 1 to 6 carbon atoms in which one or more hydrogen atoms are substituted by a fluorine group include a trifluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, a perfluorohexyl group, a 2,2,2-trifluoroethyl group, a 2,2,3,3,3-pentafluoropropyl group, a 2,2,2,2,2,2-hexafluoroisopropyl group, a 2,2,3,3,4,4,4-heptafluorobutyl group, a 2,2,3,3,4,4,5,5,5-nonafluoropentyl group, and a 2,2,3,3,4,4,5,5,6,6,6-undecafluorohexyl group.
[0088] The number of cyano groups in the alkyl group having 1 to 6 carbon atoms in which one or more hydrogen atoms are replaced by cyano groups may be 1 or 2 or more. If the number of cyano groups is large, the polarity of the fluorine-containing ether compound becomes too high, so the number of cyano groups is preferably 2 or less, and most preferably 1.
[0089] Examples of the alkyl group having 1 to 6 carbon atoms in which one or more hydrogen atoms are substituted with a cyano group include 2-cyanoethyl, 3-cyanopropyl, 4-cyanobutyl, 5-cyanopentyl, 6-cyanohexyl, 2-cyano-1-methylethyl and 2,2'-dicyanoisopropyl.
[0090] The organic group having at least one double bond or triple bond is preferably an organic group having 6 to 12 carbon atoms having an aromatic hydrocarbon, an organic group having 3 to 10 carbon atoms having an aromatic heterocycle, an alkenyl group having 2 to 8 carbon atoms, and an alkynyl group having 3 to 8 carbon atoms, and may be straight chain or branched.
[0091] Examples of the organic group having 6 to 12 carbon atoms and having an aromatic hydrocarbon include phenyl, methoxyphenyl, dimethoxyphenyl, cyanophenyl, dicyanophenyl, fluorophenyl, naphthyl, methoxynaphthyl, benzyl, methoxybenzyl, phenethyl, methoxyphenethyl, fluorophenethyl, naphthylmethyl, and naphthylethyl. However, when the aromatic hydrocarbon has a substituent, the substitution position may be anywhere.
[0092] Examples of the organic group having 3 to 10 carbon atoms and having an aromatic heterocyclic ring include pyrrolyl, pyrazolyl, methylpyrazolylmethyl, imidazolyl, furanyl, furfuryl, Azolyl, iso oxazolyl, thienyl, thienylmethyl, thienylethyl, thiazolyl, methylthiazolylethyl, isothiazolyl, pyridyl, pyrimidinyl, pyridazinyl, pyrazinyl, indolinyl, benzofuranyl, benzothienyl, benzimidazolyl, benzo Azolyl, benzothiazolyl, benzopyrazolyl, benzisophthalic acid oxazolyl, benzisothiazolyl, quinolyl, isoquinolyl, quinazolinyl, quinoxalinyl, phthalazinyl, and cinnolinyl.
[0093] Examples of the alkenyl group having 2 to 8 carbon atoms include vinyl, allyl, 1-propenyl, isopropenyl, 3-butenyl and structural isomers thereof, 4-pentenyl and structural isomers thereof, 5-hexenyl and structural isomers thereof, 6-heptenyl and structural isomers thereof, and 7-octenyl and structural isomers thereof.
[0094] Examples of the alkynyl group having 3 to 8 carbon atoms include 1-propynyl, propargyl, 3-butynyl and structural isomers thereof, 4-pentynyl and structural isomers thereof, 5-hexynyl and structural isomers thereof, 6-heptynyl and structural isomers thereof, and 7-octynyl and structural isomers thereof.
[0095] From the viewpoint of availability and / or ease of synthesis, R in the fluorinated ether compound represented by formula (1) 1Preferred are methyl, ethyl, n-propyl, isopropyl, 2,2,2-trifluoroethyl, 2,2,3,3,3-pentafluoropropyl, 2,2,2,2,2,2-hexafluoroisopropyl, 2-cyanoethyl, 3-cyanopropyl, 4-cyanobutyl, phenyl, methoxyphenyl, cyanophenyl, phenethyl, thienylethyl, N-methylpyrazolylmethyl, allyl, 3-butenyl, 4-pentenyl, propargyl, 3-butynyl, 4-pentynyl, and most preferred are methyl, ethyl, n-propyl, 2,2,2-trifluoroethyl, 2,2,3,3,3-pentafluoropropyl, 3-cyanopropyl, 4-cyanobutyl, methoxyphenyl, cyanophenyl, allyl, 3-butenyl.
[0096] In the fluorine-containing ether compound of the present embodiment, a in formula (1) is an integer of 2 to 4. b in formula (1) is 0 or 1. When b is 0, the ratio of fluorine atoms in the fluorine-containing ether compound molecule decreases, and the increase in the surface free energy of the entire molecule can be suppressed.
[0097] When b is 1, the terminal group R in formula (1) 1 The ether bond is combined with [A] represented by formula (2) via an ether bond, and the ether bond imparts flexibility to the fluorinated ether compound represented by formula (1), thereby obtaining an effect of being easily adsorbed to the protective layer. When b is 1, a is preferably an integer of 2 to 3, and more preferably 2. When a is 2, the ratio of fluorine atoms in the fluorinated ether compound molecule is reduced, which can suppress the increase of the surface free energy of the entire molecule.
[0098] In addition, if a is 1, it is chemically unstable and a tendency to be easily decomposed is observed, so a is set to an integer of 2 to 4.
[0099] In the fluorinated ether compound represented by formula (1), [A] is represented by formula (2), and [B] is a divalent linking group represented by formula (3). In formula (1), [A] and [B] together often have two secondary hydroxyl groups, and the carbon atoms to which the hydroxyl groups are bonded are bonded to each other via a linking group consisting of a methylene group (-CH2-) and an ether bond (-O-). Therefore, the distance between the hydroxyl groups of the two hydroxyl groups contained in the -[A]-[B]- structure becomes appropriate. Moreover, by having an etheric oxygen atom, the -[A]-[B]- structure imparts moderate softness to the molecular structure of the fluorinated ether compound represented by formula (1). Based on these, when a lubricating layer comprising a fluorinated ether compound of the present embodiment is formed on a protective layer, the two hydroxyl groups in the -[A]-[B]- structure are easily involved in the bonding between the active points on the protective layer and the lubricating layer. Therefore, the lubricating layer comprising a fluorinated ether compound of the present embodiment has excellent adhesion to the protective layer. As a result, adhesion and falling off can be suppressed.
[0100] In formula (2), c is 1 or 2, in formula (3), d is 0 or 1, and e is an integer of 2 to 4. The sum of the values of c and d is often 2. From the viewpoint of adhesion to the protective layer, c=2, d=0 or c=1, d=1 is preferred. In the case of c=2, d=0, the directions of the stereochemical configuration of the hydroxyl groups become the same, and a tendency for the hydroxyl groups to be easily adsorbed to the protective layer is observed. In the case of c=1, d=1, the distance between the hydroxyl groups contained in the -[A]-[B]- structure is further away from each other, which can reduce the interaction (such as hydrogen bonding) within the fluorinated ether compound represented by formula (1) and increase the affinity with the protective layer. In the case of c=1, d=1, the value of e is preferably an integer of 2 to 3, and most preferably 2.
[0101] The fluorine-containing ether compound of this embodiment has R as shown in formula (1). 2 The perfluoropolyether chain (hereinafter sometimes abbreviated as "PFPE chain") shown in FIG. 1 is a perfluoropolyether chain. When a lubricant containing a fluorinated ether compound is applied to the protective layer to form a lubricating layer, the PFPE chain covers the surface of the protective layer and imparts lubricity to the lubricating layer, thereby reducing the friction between the magnetic head and the protective layer. 2 There is no particular limitation and the fluorine-containing ether compound may be appropriately selected depending on the performance required of the lubricant containing the fluorine-containing ether compound.
[0102] Examples of the PFPE chain include PFPE chains formed of perfluoromethylene oxide polymers, perfluoroethylene oxide polymers, perfluoro-n-propylene oxide polymers, perfluoro-iso-propylene oxide polymers, and copolymers thereof.
[0103] Specifically, it is preferred that R in formula (1) 2 is any one of the following formulas (5) to (8). 2 In the case of any one of the formulae (5) to (8), it is a fluorine-containing ether compound capable of obtaining a lubricating layer having good lubricity.
[0104] It should be noted that there is no particular restriction on the arrangement order of (CF2-CF2-O) and (CF2-O) as repeating units in formula (5). In formula (5), the number g of (CF2-CF2-O) representing the average degree of polymerization and the number h of (CF2-O) may be the same or different. Formula (5) may include any of a random copolymer, a block copolymer, and an alternating copolymer formed by monomer units (CF2-CF2-O) and (CF2-O).
[0105] -CF2O-(CF2CF2O) g -(CF2O) h -CF2- (5)
[0106] (In formula (5), g and h are average polymerization degrees, g represents 3 to 8, and h represents 3 to 8.)
[0107] -CF2O-(CF2CF2O) i -CF2- (6)
[0108] (i in formula (6) is an average degree of polymerization and represents 5 to 13.)
[0109] -CF2CF2O-(CF2CF2CF2O) j -CF2CF2- (7)
[0110] (j in formula (7) is the average degree of polymerization and represents 3 to 8.)
[0111] -CF(CF3)-(OCF(CF3)CF2) k -OCF(CF3)- (8)
[0112] (k in formula (8) is an average degree of polymerization and represents 3 to 8.)
[0113] In formula (5), g, which represents the average degree of polymerization, is 3 to 8, preferably 4 to 7, and more preferably 4 to 5. h, which represents the average degree of polymerization, is 3 to 8, preferably 4 to 7, and more preferably 4 to 5.
[0114] In the formula (6), when i is 5 to 13, the number average molecular weight of the fluorine-containing ether compound of the present embodiment tends to be within a preferred range. i is preferably 6 to 10, and more preferably 6 to 8.
[0115] In formula (7), when j is 3 to 8, the number average molecular weight of the fluorine-containing ether compound of the present embodiment tends to be within a preferred range. j is preferably 3.5 to 7, and more preferably 3.5 to 5.
[0116] In the formula (8), when k is 3 to 8, the number average molecular weight of the fluorine-containing ether compound of the present embodiment tends to be in a preferred range. k is preferably 3.5 to 7, and more preferably 3.5 to 5.
[0117] In formula (1), R 2 In the case of any one of the formulae (5) to (8), the fluorine-containing ether compound can be easily synthesized, which is preferred. 2In the case of any one of formulas (5) to (8), the ratio of the number of oxygen atoms (the number of ether bonds (-O-)) in the PFPE chain to the number of carbon atoms and the arrangement of oxygen atoms in the PFPE chain become appropriate. Therefore, a fluorinated ether compound having a moderate hardness is obtained. Therefore, the fluorinated ether compound applied to the protective layer is not easily agglomerated on the protective layer, and a thinner lubricating layer can be formed with a sufficient coverage.
[0118] In particular, R in formula (1) 2 In the case of formula (5), the raw materials are easily available and thus it is more preferred.
[0119] In the fluorine-containing ether compound of the present embodiment represented by the above formula (1), R 3 is the terminal group shown in formula (4). 3 It has two secondary hydroxyl groups and one primary hydroxyl group, and the carbon atoms to which the hydroxyl groups are bonded are bonded to each other via a linking group consisting of a methylene group (-CH2-) and an ether bond (-O-). 3 The distances between the three hydroxyl groups contained in the hydroxyl groups become appropriate. 3 The molecular structure of the fluorinated ether compound represented by formula (1) imparts appropriate flexibility. Based on these, when a lubricating layer containing the fluorinated ether compound of this embodiment is formed on the protective layer, R 3 The three hydroxyl groups in the fluorinated ether compound are easy to participate in the combination of the active point on the protective layer and the lubricating layer. Therefore, the lubricating layer comprising the fluorinated ether compound of the present embodiment has excellent adhesion to the protective layer. As a result, the fluorinated ether compound that does not adhere to the protective layer (adsorption) and exists can be prevented from agglomerating and adhering to the magnetic head as a foreign matter (stain), thereby suppressing adhesion. In addition, the occurrence of the reduction of the film thickness of the lubricating layer caused by the scattering / evaporation caused by the centrifugal force and / or heat during high-speed rotation can be suppressed.
[0120] In formula (4), f is an integer of 2 to 5. f is more preferably an integer of 2 to 3, and most preferably 2.
[0121] When f is 1, the structure is stabilized by the regular arrangement of the five-membered ring-type intramolecular hydrogen bonds between the ether oxygen atoms and the hydroxyl groups in formula (4), thereby reducing the adhesion to the protective layer. When f is 2 or more, the regular arrangement is destroyed, the intramolecular interaction of the hydroxyl groups is hindered, and the adhesion to the protective layer is greatly improved. If f is 6 or more, the proportion of fluorine atoms in the fluorine-containing ether compound molecule is reduced, so the surface free energy of the entire molecule becomes large, which is not preferred.
[0122] In the fluorinated ether compound of the present embodiment represented by formula (1), the two hydroxyl groups contained in the -[A]-[B]- structure and R 3The three hydroxyl groups contained in the compound are well-balancedly arranged in R through methylene groups (-CH2-). 2 The hydroxyl groups at the ends of the PFPE chain are appropriately spaced apart and have a moderately soft structure, so they are easily involved in the bonding between the active point on the protective layer and the lubricating layer. Therefore, the fluorinated ether compound of this embodiment can be effectively adsorbed to the protective layer at the hydroxyl groups at both ends of the PFPE chain, and thus exhibits excellent adhesion properties through a synergistic effect.
[0123] Based on the above, the lubricating layer containing the fluorine-containing ether compound of the present embodiment has excellent adhesion to the protective layer. As a result, sticking and falling off can be suppressed.
[0124] Specifically, the fluorinated ether compound represented by formula (1) is preferably any one of the following formulae (A1) to (T1). It should be noted that the repetition numbers represented by ma1 to mt1 and na1 to nt1 in formulae (A1) to (T1) are values indicating the average degree of polymerization and are therefore not necessarily integers.
[0125]
[0126] (In formula (A1), ma1 and na1 represent average polymerization degrees, ma1 is 3 to 8, and na1 is 3 to 8.)
[0127] (In formula (A2), na2 represents the average degree of polymerization, and na2 is 5 to 13.)
[0128] (In formula (A3), na3 represents the average degree of polymerization, and na3 is 3 to 8.)
[0129]
[0130] (In formula (B1), mb1 and nb1 represent average polymerization degrees, mb1 is 3 to 8, and nb1 is 3 to 8.)
[0131] (In formula (B2), nb2 represents the average degree of polymerization, and nb2 is 5 to 13.)
[0132] (In formula (B3), nb3 represents the average degree of polymerization, and nb3 is 3 to 8.)
[0133]
[0134] (In formula (C1), mc1 and nc1 represent average polymerization degrees, mc1 is 3 to 8, and nc1 is 3 to 8.)
[0135] (In formula (D1), md1 and nd1 represent average polymerization degrees, md1 is 3 to 8, and nd1 is 3 to 8.)
[0136] (In formula (E1), me1 and ne1 represent average polymerization degrees, me1 is 3 to 8, and ne1 is 3 to 8.)
[0137] (In formula (F1), mf1 and nf1 represent average polymerization degrees, mf1 is 3 to 8, and nf1 is 3 to 8.)
[0138]
[0139] (In formula (G1), mg1 and ng1 represent average polymerization degrees, and mg1 is 3 to 8 and ng1 is 3 to 8.)
[0140] (In formula (H1), mh1 and nh1 represent average polymerization degrees, mh1 is 3 to 8, and nh1 is 3 to 8.)
[0141]
[0142] (In formula (I1), mi1 and ni1 represent average polymerization degrees, mi1 is 3 to 8, and ni1 is 3 to 8.)
[0143] (In formula (J1), mj1 and nj1 represent the average degree of polymerization, mj1 is 3 to 8, and nj1 is 3 to 8.)
[0144] (In formula (K1), mk1 and nk1 represent average polymerization degrees, mk1 is 3 to 8, and nk1 is 3 to 8.)
[0145] (In formula (L1), ml1 and nl1 represent average polymerization degrees, ml1 is 3 to 8, and nl1 is 3 to 8.)
[0146]
[0147] (In formula (M1), mm1 and nm1 represent the average degree of polymerization, mm1 is 3 to 8, and nm1 is 3 to 8.)
[0148] (In formula (N1), mn1 and nn1 represent average polymerization degrees, mn1 is 3 to 8, and nn1 is 3 to 8.)
[0149]
[0150] (In formula (O1), mo1 and no1 represent average polymerization degrees, mo1 is 3 to 8, and no1 is 3 to 8.)
[0151] (In formula (P1), mp1 and np1 represent average polymerization degrees, mp1 is 3 to 8, and np1 is 3 to 8.)
[0152]
[0153] (In formula (Q1), mq1 and nq1 represent the average degree of polymerization, mq1 is 3 to 8, and nq1 is 3 to 8.)
[0154] (In formula (R1), mr1 and nr1 represent the average degree of polymerization, mr1 is 3 to 8, and nr1 is 3 to 8.)
[0155]
[0156] (In formula (S1), ms1 and ns1 represent the average degree of polymerization, ms1 is 3 to 8, and ns1 is 3 to 8.)
[0157] (In formula (T1), mt1 and nt1 represent average polymerization degrees, mt1 is 3 to 8, and nt1 is 3 to 8.)
[0158] The number average molecular weight (Mn) of the fluorine-containing ether compound of the present embodiment is preferably in the range of 1000 to 2300, more preferably in the range of 1100 to 2100, particularly preferably in the range of 1200 to 1800, and most preferably in the range of 1200 to 1600.
[0159] If the number average molecular weight is more than 1000, the lubricant containing the fluorine-containing ether compound of the present embodiment is not easy to evaporate. Therefore, if the number average molecular weight is more than 1000, adhesion and falling off can be prevented. In addition, if the number average molecular weight is less than 2300, the viscosity of the fluorine-containing ether compound will not become too high, and become a viscosity suitable for use as a lubricant. It should be noted that if the number average molecular weight exceeds 2300, the viscosity of the fluorine-containing ether compound becomes high, and a tendency of poor operation is observed.
[0160] From the perspective of the availability of raw materials for PFPE chains, the number average molecular weight is preferably in the range of 1100 to 2100. If the number average molecular weight is in the range of 1200 to 1800, the coverage does not deteriorate even if the film thickness of the lubricating layer is reduced, and the chemical resistance and wear resistance can be maintained. If the number average molecular weight is in the range of 1200 to 1600, the performance balance is the best from the perspective of preventing sticking and falling off and thinning the lubricating layer.
[0161] "Manufacturing method"
[0162] The method for producing the fluorine-containing ether compound of the present embodiment is not particularly limited, and the fluorine-containing ether compound of the present embodiment can be produced by a conventionally known production method. The fluorine-containing ether compound of the present embodiment can be produced, for example, by the production method described below.
[0163] First, prepare a 2 The corresponding PFPE chain has a fluorine compound with a hydroxymethyl group (-CH2OH) at both ends of the molecule.
[0164] Next, the hydroxyl group of the hydroxymethyl group disposed at one end of the fluorine-based compound is replaced by R 1 -(O(CH2) a ) b Then, the hydroxyl group of the hydroxymethyl group at the other end is replaced by -R in formula (1). 3 The terminal group formed (second reaction).
[0165] The first reaction and the second reaction can be carried out by conventionally known methods, and can be appropriately determined according to the type of the terminal in formula (1), etc. In addition, either the first reaction or the second reaction may be carried out first.
[0166] [Lubricant for magnetic recording media]
[0167] The lubricant for a magnetic recording medium according to the present embodiment contains a fluorine-containing ether compound represented by formula (1).
[0168] The lubricant of the present embodiment may be mixed with a known material used as a lubricant material as needed, as long as the properties due to the inclusion of the fluorine-containing ether compound represented by the formula (1) are not impaired.
[0169] Specific examples of known materials include FOMBLIN (registered trademark) ZDIAC, FOMBLIN ZDEAL, FOMBLIN AM-2001 (all manufactured by Solvay Solexis), Moresco A20H (manufactured by Moresco), etc. The known material used in combination with the lubricant of the present embodiment preferably has a number average molecular weight of 1,000 to 10,000.
[0170] When the lubricant of the present embodiment contains a material other than the fluorinated ether compound represented by formula (1), the content of the fluorinated ether compound represented by formula (1) in the lubricant of the present embodiment is preferably 50% by mass or more, more preferably 70% by mass or more. The content of the fluorinated ether compound represented by formula (1) may also be 80% by mass or more, or 90% by mass or more.
[0171] Since the lubricant of the present embodiment contains the fluorine-containing ether compound represented by the formula (1), it is possible to obtain a lubricating layer having good adhesion to the protective layer and capable of suppressing sticking and peeling even when the molecular weight is reduced.
[0172] [Magnetic recording media]
[0173] The magnetic recording medium of this embodiment includes at least a magnetic layer, a protective layer, and a lubricating layer provided in this order on a substrate.
[0174] In the magnetic recording medium of this embodiment, one or more underlayers may be provided between the substrate and the magnetic layer as required. In addition, an adhesion layer and / or a soft magnetic layer may be provided between the underlayer and the substrate.
[0175] Figure 1 This is a schematic cross-sectional view showing one embodiment of the magnetic recording medium of this embodiment.
[0176] The magnetic recording medium 10 of the present embodiment has a structure in which an adhesion layer 12 , a soft magnetic layer 13 , a first underlayer 14 , a second underlayer 15 , a magnetic layer 16 , a protective layer 17 , and a lubricating layer 18 are sequentially provided on a substrate 11 .
[0177] "Substrate"
[0178] As the substrate 11 , for example, a non-magnetic substrate in which a film made of NiP or a NiP alloy is formed on a base made of a metal or alloy material such as Al or an Al alloy can be used.
[0179] In addition, as the substrate 11, a non-magnetic substrate formed of a non-metallic material such as glass, ceramics, silicon, silicon carbide, carbon, or resin can be used, or a non-magnetic substrate having a film of NiP or NiP alloy formed on a base formed of these non-metallic materials can be used.
[0180] Glass substrates are suitable for high recording density because they are rigid and smooth. Examples of glass substrates include aluminosilicate glass substrates, and chemically strengthened aluminosilicate glass substrates are particularly suitable.
[0181] The roughness of the main surface of the substrate 11 is preferably ultra-smooth with Rmax of 6 nm or less and Ra of 0.6 nm or less. It should be noted that the surface roughness Rmax and Ra referred to here are based on the provisions of JIS B0601.
[0182] "Attachment Layer"
[0183] The adhesive layer 12 prevents the substrate 11 from being corroded when the substrate 11 and the soft magnetic layer 13 provided on the adhesive layer 12 are arranged in contact with each other.
[0184] The material of the adhesion layer 12 can be appropriately selected from, for example, Cr, Cr alloy, Ti, Ti alloy, CrTi, NiAl, AlRu alloy, etc. The adhesion layer 12 can be formed by, for example, sputtering.
[0185] "Soft magnetic layer"
[0186] The soft magnetic layer 13 preferably has a structure in which a first soft magnetic film, an intermediate layer composed of a Ru film, and a second soft magnetic film are stacked in sequence. That is, the soft magnetic layer 13 preferably has a structure in which the upper and lower soft magnetic films of the intermediate layer are antiferrocoupled (AFC) by sandwiching an intermediate layer composed of a Ru film between two soft magnetic films.
[0187] Examples of the material of the first soft magnetic film and the second soft magnetic film include CoZrTa alloy and CoFe alloy.
[0188] Preferably, any one of Zr, Ta, and Nb is added to the CoFe alloy used in the first soft magnetic film and the second soft magnetic film. Thus, the amorphization of the first soft magnetic film and the second soft magnetic film is promoted, and the orientation of the first base layer (seed layer) can be improved. At the same time, the floating amount of the magnetic head can be reduced.
[0189] The soft magnetic layer 13 can be formed by, for example, sputtering.
[0190] "1st base layer"
[0191] The first underlayer 14 is a layer for controlling the orientation and crystal size of the second underlayer 15 and the magnetic layer 16 provided thereon.
[0192] Examples of the first base layer 14 include a Cr layer, a Ta layer, a Ru layer, a CrMo alloy layer, a CoW alloy layer, a CrW alloy layer, a CrV alloy layer, and a CrTi alloy layer.
[0193] The first base layer 14 can be formed by, for example, sputtering.
[0194] "Second base layer"
[0195] The second underlayer 15 is a layer that is controlled so as to improve the orientation of the magnetic layer 16. The second underlayer 15 is preferably a layer formed of Ru or a Ru alloy.
[0196] The second base layer 15 may be composed of a single layer or a plurality of layers. When the second base layer 15 is composed of a plurality of layers, all layers may be composed of the same material, or at least one layer may be composed of a different material.
[0197] The second base layer 15 can be formed by, for example, sputtering.
[0198] "Magnetic layer"
[0199] The magnetic layer 16 is composed of a magnetic film whose easy magnetization axis is oriented vertically or horizontally with respect to the substrate surface. The magnetic layer 16 is a layer containing Co and Pt, and may also be a layer containing oxides, Cr, B, Cu, Ta, Zr, etc., in order to further improve the SNR (Signal to Noise Ratio) characteristics.
[0200] Examples of the oxide contained in the magnetic layer 16 include SiO 2 , SiO, Cr 2 O 3 , CoO, Ta 2 O 3 , and TiO 2 .
[0201] The magnetic layer 16 may be composed of a single layer or a plurality of magnetic layers formed of materials having different compositions.
[0202] For example, when the magnetic layer 16 is composed of three layers, namely, the first magnetic layer, the second magnetic layer, and the third magnetic layer, which are stacked in order from the bottom, the first magnetic layer is preferably a granular structure formed by a material containing Co, Cr, Pt, and further containing an oxide. As the oxide contained in the first magnetic layer, it is preferred to use, for example, oxides of Cr, Si, Ta, Al, Ti, Mg, Co, etc. Among them, in particular, TiO2, Cr2O3, SiO2, etc. can be used appropriately. In addition, the first magnetic layer is preferably formed by a composite oxide to which two or more oxides are added. In particular, Cr2O3-SiO2, Cr2O3-TiO2, SiO2-TiO2, etc. can be used appropriately.
[0203] The first magnetic layer may contain one or more elements selected from B, Ta, Mo, Cu, Nd, W, Nb, Sm, Tb, Ru, and Re in addition to Co, Cr, Pt, and oxides. The same material as that of the first magnetic layer may be used for the second magnetic layer. The second magnetic layer preferably has a granular structure.
[0204] The third magnetic layer is preferably a non-granular structure formed of a material containing Co, Cr, and Pt and containing no oxide. In addition to Co, Cr, and Pt, the third magnetic layer may contain one or more elements selected from B, Ta, Mo, Cu, Nd, W, Nb, Sm, Tb, Ru, Re, and Mn.
[0205] When the magnetic layer 16 is formed of a plurality of magnetic layers, a non-magnetic layer is preferably provided between adjacent magnetic layers. When the magnetic layer 16 is composed of three layers, namely, a first magnetic layer, a second magnetic layer, and a third magnetic layer, a non-magnetic layer is preferably provided between the first magnetic layer and the second magnetic layer, and between the second magnetic layer and the third magnetic layer.
[0206] The non-magnetic layer of the magnetic layer 16 arranged between adjacent magnetic layers can be suitably made of, for example, Ru, Ru alloy, CoCr alloy, CoCrX1 alloy (X1 represents one or more elements selected from Pt, Ta, Zr, Re, Ru, Cu, Nb, Ni, Mn, Ge, Si, O, N, W, Mo, Ti, V, and B), etc.
[0207] It is preferable to use an alloy material containing oxide, metal nitride, or metal carbide in the non-magnetic layer provided between adjacent magnetic layers of the magnetic layer 16. Specifically, as oxides, for example, SiO2, Al2O3, Ta2O5, Cr2O3, MgO, Y2O3, TiO2, etc. can be used. As metal nitrides, for example, AlN, Si3N4, TaN, CrN, etc. can be used. As metal carbides, for example, TaC, BC, SiC, etc. can be used.
[0208] The non-magnetic layer can be formed by, for example, sputtering.
[0209] In order to achieve a higher recording density, the magnetic layer 16 is preferably a perpendicular magnetic recording magnetic layer in which the easy magnetization axis is oriented perpendicular to the substrate surface. The magnetic layer 16 may also be an in-plane magnetic recording magnetic layer.
[0210] The magnetic layer 16 can be formed by any conventionally known method such as vapor deposition, ion beam sputtering, magnetron sputtering, etc. The magnetic layer 16 can usually be formed by sputtering.
[0211] "Protective layer"
[0212] The protective layer 17 protects the magnetic layer 16. The protective layer 17 may be composed of a single layer or a plurality of layers. Examples of the material of the protective layer 17 include carbon, carbon containing nitrogen, silicon carbide, and the like.
[0213] As the protective layer 17, a carbon protective layer can be preferably used, and an amorphous carbon protective layer is particularly preferred. If the protective layer 17 is a carbon protective layer, the interaction with the polar group (especially hydroxyl group) contained in the fluorine-containing ether compound in the lubricating layer 18 is further improved, so it is preferred. The adhesion between the carbon protective layer and the lubricating layer 18 can be controlled by making the carbon protective layer hydrogenated carbon and / or carbon nitride and adjusting the hydrogen content and / or nitrogen content in the carbon protective layer.
[0214] The hydrogen content in the carbon-based protective layer is preferably 3 to 20 atomic % when measured by hydrogen forward scattering (HFS), and the nitrogen content in the carbon-based protective layer is preferably 4 to 12 atomic % when measured by X-ray photoelectron spectroscopy (XPS).
[0215] The hydrogen and / or nitrogen contained in the carbon-based protective layer does not need to be uniformly contained in the entire carbon-based protective layer. It is suitable to make the carbon-based protective layer, for example, a composition gradient layer in which the lubricating layer 18 side of the protective layer 17 contains nitrogen and the magnetic layer 16 side of the protective layer 17 contains hydrogen. In this case, the adhesion between the magnetic layer 16 and the lubricating layer 18 and the carbon-based protective layer is further improved. This is because the nitrogen in the protective layer 17 acts as an active point and promotes the bonding with the lubricating layer. The hydrogen or nitrogen in the carbon-based protective layer has the function of acting as an active point.
[0216] The protective layer 17 preferably has a thickness of 1 nm to 7 nm. When the protective layer 17 has a thickness of 1 nm or more, sufficient performance as the protective layer 17 can be obtained. When the protective layer 17 has a thickness of 7 nm or less, this is preferred from the viewpoint of reducing the thickness of the protective layer 17.
[0217] As a method for forming the protective layer 17 , a sputtering method using a target containing carbon, a CVD (chemical vapor deposition) method using a hydrocarbon raw material such as ethylene or toluene, an IBD (ion beam deposition) method, or the like can be used.
[0218] When a carbon-based protective layer is formed as the protective layer 17, for example, a DC magnetron sputtering method can be used for film formation. In particular, when a carbon-based protective layer is formed as the protective layer 17, it is preferred that an amorphous carbon protective layer be formed by a plasma CVD method. The surface of the amorphous carbon protective layer formed by the plasma CVD method is uniform and has little roughness.
[0219] "Lubricating layer"
[0220] The lubricating layer 18 prevents contamination of the magnetic recording medium 10. In addition, the lubricating layer 18 reduces the frictional force of the magnetic head of the magnetic recording and reproducing device sliding on the magnetic recording medium 10, thereby improving the durability of the magnetic recording medium 10.
[0221] Lubricating layer 18 Figure 1 As shown, the lubricating layer 18 is formed in contact with the protective layer 17. The lubricating layer 18 contains the fluorine-containing ether compound of this embodiment.
[0222] When the protective layer 17 disposed under the lubricating layer 18 is a carbon-based protective layer, the lubricating layer 18 is particularly bonded with the protective layer 17 with a high bonding force. As a result, it is easy to obtain a magnetic recording medium 10 in which the surface of the protective layer 17 is coated with a high coverage rate even if the thickness of the lubricating layer 18 is thin, and contamination of the surface of the magnetic recording medium 10 can be effectively prevented.
[0223] The average film thickness of the lubricating layer 18 is preferably More preferably If the average film thickness of the lubricating layer 18 is more than 0.5nm, the lubricating layer 18 is not in an island shape or a mesh shape but is formed with a uniform film thickness. Therefore, the surface of the protective layer 17 can be coated with a high coverage rate by the lubricating layer 18. In addition, by making the average film thickness of the lubricating layer 18 less than 3.0nm, the lubricating layer 18 can be fully filmized to make the floating amount of the magnetic head fully small.
[0224] When the surface of the protective layer 17 is not covered with a sufficiently high coverage rate by the lubricating layer 18, the environmental substances adsorbed on the surface of the magnetic recording medium 10 penetrate through the gaps of the lubricating layer 18 and intrude under the lubricating layer 18. The environmental substances intruding into the lower layer of the lubricating layer 18 are adsorbed and combined with the protective layer 17 to generate pollutants. Furthermore, during magnetic recording and reproducing, the pollutants (agglomerated components) are attached (transferred) to the magnetic head as stains, causing damage to the magnetic head or reducing the magnetic recording and reproducing characteristics of the magnetic recording and reproducing device.
[0225] Environmental substances that cause pollutants to be generated include, for example, siloxane compounds (cyclic siloxane, linear siloxane), ionic impurities, hydrocarbons with high molecular weight such as octacosane, plasticizers such as dioctyl phthalate, etc. Metal ions included in ionic impurities include, for example, sodium ions, potassium ions, etc. Inorganic ions included in ionic impurities include, for example, chloride ions, bromide ions, nitrate ions, sulfate ions, ammonium ions, etc. Organic ions included in ionic impurities include, for example, oxalate ions, formate ions, etc.
[0226] "Method for forming a lubricating layer"
[0227] Examples of a method for forming the lubricating layer 18 include a method of preparing a magnetic recording medium in which each layer up to the protective layer 17 is formed on the substrate 11 , applying a lubricating layer forming solution on the protective layer 17 , and drying the solution.
[0228] The lubricant layer-forming solution is obtained by dispersing and dissolving the lubricant for a magnetic recording medium of the above-described embodiment in a solvent as necessary, and adjusting the solution to a viscosity and a concentration suitable for a coating method.
[0229] Examples of the solvent used for the lubricating layer-forming solution include fluorine-based solvents such as Batler (registered trademark) XF (trade name, manufactured by DuPont Mitsui Fluoro Chemical Co., Ltd.).
[0230] The coating method of the lubricating layer forming solution is not particularly limited, and examples thereof include a spin coating method, a spray method, a paper coating method, and a dipping method.
[0231] When the dipping method is used, for example, the following method can be used. First, the substrate 11 on which each layer up to the protective layer 17 is formed is dipped in the lubricating layer forming solution put into the dipping tank of the dipping coating device. Then, the substrate 11 is pulled out of the dipping tank at a predetermined speed. Thus, the lubricating layer forming solution is applied to the surface of the substrate 11 on the protective layer 17.
[0232] By using the dipping method, the lubricating layer-forming solution can be uniformly applied to the surface of the protective layer 17 , and the lubricating layer 18 can be formed on the protective layer 17 with a uniform film thickness.
[0233] In the present embodiment, it is preferable to perform heat treatment on the substrate 11 on which the lubricating layer 18 is formed. By performing the heat treatment, the adhesion between the lubricating layer 18 and the protective layer 17 is improved, and the adhesion between the lubricating layer 18 and the protective layer 17 is improved.
[0234] The heat treatment temperature is preferably 100 to 180° C. If the heat treatment temperature is 100° C. or higher, the effect of improving the adhesion between the lubricating layer 18 and the protective layer 17 is sufficiently obtained. In addition, if the heat treatment temperature is 180° C. or lower, thermal decomposition of the lubricating layer 18 can be prevented. The heat treatment time is preferably 10 to 120 minutes.
[0235] In the present embodiment, in order to further improve the adhesion of the lubricating layer 18 to the protective layer 17 , a treatment of irradiating the lubricating layer 18 of the substrate 11 before or after the heat treatment with ultraviolet rays (UV) may be performed.
[0236] The magnetic recording medium 10 of this embodiment has at least a magnetic layer 16, a protective layer 17, and a lubricating layer 18 sequentially provided on a substrate 11. In the magnetic recording medium 10 of this embodiment, the lubricating layer 18 containing the fluorine-containing ether compound is formed on the protective layer 17 in contact with each other.
[0237] It is difficult to reduce the thickness of the lubricating layer of conventional lubricants while maintaining the reliability and durability of magnetic recording media. Even when attempts have been made to reduce the molecular weight of the fluorine-containing ether compound used in the lubricant in order to reduce the thickness, there has been a problem of peeling.
[0238] Since the lubricant of the present embodiment contains the fluorine-containing ether compound represented by the formula (1), it is possible to form a lubricating layer that can suppress sticking and peeling even when the molecular weight is reduced.
[0239] Therefore, the lubricating layer 18 of the present embodiment has good adhesion to the protective layer, and can suppress adhesion and falling off even if the molecular weight is low. Therefore, the magnetic recording medium 10 of the present embodiment has excellent reliability and durability. In addition, according to the lubricating layer 18 of the present embodiment, it is possible to seek a further reduction in magnetic spacing, which can contribute to the improvement of the recording density of the magnetic recording medium. Therefore, the magnetic recording medium 10 of the present embodiment is particularly suitable as a magnetic disk mounted on a magnetic disk device of the LUL method (Load Unload method).
[0240] Example
[0241] The present invention will be described in more detail below by way of examples and comparative examples. It should be noted that the present invention is not limited to the following examples.
[0242] [NMR measurement method]
[0243] The structures of the compounds obtained in Examples 1 to 54 below were identified by using AVANCE III-400 manufactured by Bruker Biospin. 1 H-NMR and 19 F-NMR measurement was performed.
[0244] About 10 mg of a sample used for NMR measurement was weighed, dissolved in about 0.5 mL of deuterated acetone (hexafluorobenzene was added as a reference substance), and used for measurement. 1 The standard of H-NMR chemical shift was set to the peak of acetone at 2.05 ppm. 19 The standard of the F-NMR chemical shift was the peak of hexafluorobenzene at -164.7 ppm.
[0245] The number average molecular weight of each compound shown in Tables 2 to 4 is 19 Specifically, the results of F-NMR measurement are calculated. 19 The number average molecular weight was determined by calculating the number of repeating units of the PFPE chain from the integrated intensity of fluorine atoms measured by F-NMR.
[0246] [Example 1]
[0247] The compound (A1) represented by the above formula (A1) was obtained by the method shown below (in the formula (A1), ma1 representing the average degree of polymerization was 3.4, and na1 representing the average degree of polymerization was 3.4).
[0248] First, a compound represented by the following formula (10) is synthesized by the method shown below. Two equivalents of 3-butene-1-ol and one equivalent of epichlorohydrin are reacted to synthesize a compound (9) represented by the following formula (9). The obtained compound (9) is reacted with 3,4-dihydro-2H-pyran, the hydroxyl group is protected with a tetrahydropyranyl group, and then the double bond on one side is oxidized using m-chloroperbenzoic acid to synthesize a compound (10) represented by the following formula (10).
[0249]
[0250] In addition, a compound represented by the following formula (12) was synthesized by the method shown below. The primary hydroxyl group of 3-allyloxy-1,2-propanediol was protected with a tert-butyldimethylsilyl group. Then, the secondary hydroxyl group was protected with a methoxymethyl group, and the tert-butyldimethylsilyl group was removed from the obtained compound to synthesize a compound (11) represented by the following formula (11). After reacting 2-(3-chloropropoxy)tetrahydropyran with the obtained compound (11), the double bond was oxidized using m-chloroperbenzoic acid to synthesize a compound (12) represented by the following formula (12).
[0251]
[0252] Under nitrogen atmosphere, add HOCH2CF2O (CF2CF2O) into a 200 mL eggplant flask. g (CF2O) h A fluoropolyether represented by CF2CH2OH (wherein, g representing the average degree of polymerization is 3.4, and h representing the average degree of polymerization is 3.4) (number average molecular weight 800, molecular weight distribution 1.1) (40.0 g), a compound (10) represented by the above formula (10) (9.01 g), and t-BuOH (tert-butyl alcohol) (40.0 mL) were stirred at room temperature until they became uniform. Furthermore, t-BuOK (potassium tert-butylate) (1.68 g) was added to the above eggplant flask, heated to 70°C, and stirred for 12 hours to react.
[0253] Then, the obtained reaction product was cooled to 25°C, water was added, and Batler (registered trademark) XF (hereinafter sometimes referred to as "Battler XF") manufactured by Mitsui Dupont Fluoro Chemika was further added as a solvent to extract the organic layer, which was washed with water. Anhydrous sodium sulfate was added to the organic layer for dehydration, and after filtering and separating the desiccant, the filtrate was concentrated. The residue was purified by silica gel column chromatography to obtain compound (13) (22.0 g) represented by the following formula (13).
[0254]
[0255] (In formula (13), m, which represents the average degree of polymerization, is 3.4, and n, which represents the average degree of polymerization, is 3.4.)
[0256] In a 200 mL eggplant flask under a nitrogen atmosphere, the compound (13) represented by the above formula (13) (22.0 g), the compound (12) represented by the above formula (12) (7.36 g), and t-BuOH (tert-butyl alcohol) (65.0 mL) were added and stirred at room temperature until the mixture became uniform. Furthermore, t-BuOK (potassium tert-butylate) (0.67 g) was added to the above eggplant flask, heated to 70° C., and stirred for 16 hours to react.
[0257] Then, the obtained reaction product was cooled to 25°C, and a 7% hydrogen chloride / methanol reagent (104.2 g) was added thereto, followed by stirring at room temperature for 3 hours to carry out a deprotection reaction.
[0258] The obtained reaction product was added to 7% sodium bicarbonate water (250 mL) for neutralization, and then the organic layer was extracted by adding Batler XF and washed with water. Anhydrous sodium sulfate was added to the organic layer for dehydration, and the desiccant was separated by filtration, and the filtrate was concentrated. The residue was purified by silica gel column chromatography to obtain 17.1 g of compound (A1).
[0259] The obtained compound (A1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0260] 1 H-NMR (acetone-d6): δ [ppm] = 1.58-1.82 (4H), 2.34 (2H), 3.48-4.20 (35H), 4.98 (1H), 5.05 (1H), 5.82 (1H)
[0261] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0262] [Example 2]
[0263] The compound (A1) represented by the above formula (A1) was obtained by the method shown below (in the formula (A1), ma1 representing the average degree of polymerization was 6.2, and na1 representing the average degree of polymerization was 6.2).
[0264] Instead of HOCH2CF2O (CF2CF2O) in Example 1 g (CF2O)h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h The same operation as in Example 1 was carried out to obtain 14.8 g of compound (A1) by adding a fluoropolyether (number average molecular weight 1300, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 6.2, and h representing the average polymerization degree is 6.2).
[0265] The obtained compound (A1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0266] 1 H-NMR (acetone-d6): δ [ppm] = 1.58-1.82 (4H), 2.34 (2H), 3.48-4.20 (35H), 4.98 (1H), 5.05 (1H), 5.82 (1H)
[0267] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (12.4F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (24.8F)
[0268] [Example 3]
[0269] The compound (A1) represented by the above formula (A1) was obtained by the method shown below (in the formula (A1), ma1 representing the average degree of polymerization was 7.8, and na1 representing the average degree of polymerization was 7.8).
[0270] Instead of HOCH2CF2O (CF2CF2O) in Example 1 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) hThe same operation as in Example 1 was carried out to obtain 14.2 g of compound (A1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 7.8, and h representing the average polymerization degree is 7.8).
[0271] The obtained compound (A1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0272] 1 H-NMR (acetone-d6): δ [ppm] = 1.58-1.82 (4H), 2.34 (2H), 3.48-4.20 (35H), 4.98 (1H), 5.05 (1H), 5.82 (1H)
[0273] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0274] [Example 4]
[0275] The compound (A2) represented by the above formula (A2) was obtained by the method shown below (in the formula (A2), na2 representing the average degree of polymerization was 5.4).
[0276] Instead of HOCH2CF2O (CF2CF2O) in Example 1 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. i The same operation as in Example 1 was carried out except that 13.4 g of compound (A2) was obtained by adding a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, i representing the average polymerization degree is 5.4).
[0277] The obtained compound (A2) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0278] 1H-NMR (acetone-d6): δ [ppm] = 1.59-1.81 (4H), 2.34 (2H), 3.40-4.20 (35H), 4.99 (1H), 5.08 (1H), 5.84 (1H)
[0279] 19 F-NMR (acetone-d6): δ [ppm] = -78.57 (4F), -88.92 to -89.57 (21.6F)
[0280] [Example 5]
[0281] The compound (A2) represented by the above formula (A2) was obtained by the method shown below (in the formula (A2), na2 representing the average degree of polymerization was 9.7).
[0282] Instead of HOCH2CF2O (CF2CF2O) in Example 1 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. i The same operation as in Example 1 was carried out except that 12.4 g of compound (A2) was obtained by adding a fluoropolyether (number average molecular weight 1300, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, i representing the average polymerization degree is 9.7).
[0283] The obtained compound (A2) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0284] 1 H-NMR (acetone-d6): δ [ppm] = 1.59-1.81 (4H), 2.34 (2H), 3.40-4.20 (35H), 4.99 (1H), 5.08 (1H), 5.84 (1H)
[0285] 19 F-NMR (acetone-d6): δ [ppm] = -78.57 (4F), -88.92 to -89.57 (38.8F)
[0286] [Example 6]
[0287] The compound (A2) represented by the above formula (A2) was obtained by the method shown below (in the formula (A2), na2 representing the average degree of polymerization was 12.3).
[0288] Instead of HOCH2CF2O (CF2CF2O) in Example 1 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. i The same operation as in Example 1 was carried out except that 11.1 g of compound (A2) was obtained by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein i representing the average polymerization degree is 12.3).
[0289] The obtained compound (A2) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0290] 1 H-NMR (acetone-d6): δ [ppm] = 1.59-1.81 (4H), 2.34 (2H), 3.40-4.20 (35H), 4.99 (1H), 5.08 (1H), 5.84 (1H)
[0291] 19 F-NMR (acetone-d6): δ [ppm] = -78.57 (4F), -88.92 to -89.57 (49.2F)
[0292] [Example 7]
[0293] The compound (A3) represented by the above formula (A3) was obtained by the method shown below (in the formula (A3), na3 indicating the average degree of polymerization was 3.1).
[0294] Instead of HOCH2CF2O (CF2CF2O) in Example 1 g (CF2O) h A fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g representing the average degree of polymerization is 3.4, and h representing the average degree of polymerization is 3.4) was used, while HOCH2CF2CF2O (CF2CF2CF2O) was used. j The same operation as in Example 1 was carried out except that 13.6 g of compound (A3) was obtained by adding a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) (40.0 g) represented by CF2CF2CH2OH (wherein j representing the average polymerization degree is 3.1).
[0295] The obtained compound (A3) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0296] 1 H-NMR (acetone-d6): δ [ppm] = 1.58-1.82 (4H), 2.34 (2H), 3.38-4.25 (35H), 4.98 (1H), 5.08 (1H), 5.82 (1H)
[0297] 19 F-NMR (acetone-d6): δ [ppm] = -84.22 (12.4F), -86.40 (4F), -124.30 (4F), -130.08 (6.2F)
[0298] [Example 8]
[0299] The compound (A3) represented by the above formula (A3) was obtained by the method shown below (in the formula (A3), na3 indicating the average degree of polymerization was 6.2).
[0300] Instead of HOCH2CF2O (CF2CF2O) in Example 1 g (CF2O) h A fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g representing the average degree of polymerization is 3.4, and h representing the average degree of polymerization is 3.4) was used, while HOCH2CF2CF2O (CF2CF2CF2O) was used. j The same operation as in Example 1 was carried out except that 14.1 g of compound (A3) was obtained by adding a fluoropolyether (number average molecular weight 1300, molecular weight distribution 1.1) (40.0 g) represented by CF2CF2CH2OH (wherein j representing the average polymerization degree is 6.2).
[0301] The obtained compound (A3) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0302] 1 H-NMR (acetone-d6): δ [ppm] = 1.58-1.82 (4H), 2.34 (2H), 3.38-4.25 (35H), 4.98 (1H), 5.08 (1H), 5.82 (1H)
[0303] 19F-NMR (acetone-d6): δ [ppm] = -84.22 (24.8F), -86.40 (4F), -124.30 (4F), -130.08 (12.4F)
[0304] [Example 9]
[0305] The compound (A3) represented by the above formula (A3) was obtained by the method shown below (in the formula (A3), na3 indicating the average degree of polymerization is 8).
[0306] Instead of HOCH2CF2O (CF2CF2O) in Example 1 g (CF2O) h A fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g representing the average degree of polymerization is 3.4, and h representing the average degree of polymerization is 3.4) was used, while HOCH2CF2CF2O (CF2CF2CF2O) was used. j The same operation as in Example 1 was carried out except that 11.1 g of compound (A3) was obtained by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CF2CH2OH (wherein j representing the average polymerization degree is 8).
[0307] The obtained compound (A3) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0308] 1 H-NMR (acetone-d6): δ [ppm] = 1.58-1.82 (4H), 2.34 (2H), 3.38-4.25 (35H), 4.98 (1H), 5.08 (1H), 5.82 (1H)
[0309] 19 F-NMR (acetone-d6): δ [ppm] = -84.22 (32F), -86.40 (4F), -124.30 (4F), -130.08 (16F)
[0310] [Example 10]
[0311] The compound (B1) represented by the above formula (B1) was obtained by the method shown below (in the formula (B1), mb1 representing the average degree of polymerization was 3.4, and nb1 representing the average degree of polymerization was 3.4).
[0312] First, a compound (15) represented by the following formula (15) is synthesized by the method shown below. 1,3-Diallyloxy-2-propanol is reacted with 3,4-dihydro-2H-pyran to synthesize a compound represented by the following formula (14). The double bond on one side of the obtained compound (14) is oxidized using m-chloroperbenzoic acid to synthesize a compound (15) represented by the following formula (15).
[0313]
[0314] The same procedures as in Example 1 were carried out except that the compound (15) (8.17 g) represented by the formula (15) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 16.7 g of the compound (B1).
[0315] The obtained compound (B1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0316] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0317] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0318] [Example 11]
[0319] The compound (B1) represented by the above formula (B1) was obtained by the method shown below (in the formula (B1), mb1 representing the average degree of polymerization was 6.2, and nb1 representing the average degree of polymerization was 6.2).
[0320] Instead of HOCH2CF2O (CF2CF2O) in Example 10 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) hThe same operation as in Example 10 was carried out to obtain 16.2 g of compound (B1) by adding a fluoropolyether (number average molecular weight 1300, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 6.2, and h representing the average polymerization degree is 6.2).
[0321] The obtained compound (B1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0322] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0323] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (12.4F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (24.8F)
[0324] [Example 12]
[0325] The compound (B1) represented by the above formula (B1) was obtained by the method shown below (in the formula (B1), mb1 representing the average degree of polymerization was 7.8, and nb1 representing the average degree of polymerization was 7.8).
[0326] Instead of HOCH2CF2O (CF2CF2O) in Example 10 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h The same operation as in Example 10 was carried out to obtain 16.8 g of compound (B1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 7.8, and h representing the average polymerization degree is 7.8).
[0327] The obtained compound (B1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0328] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0329] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0330] [Example 13]
[0331] The compound (B2) represented by the above formula (B2) was obtained by the method shown below (in the formula (B2), nb2 representing the average degree of polymerization was 5.4).
[0332] Instead of HOCH2CF2O (CF2CF2O) in Example 10 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. i The same operation as in Example 10 was carried out except that 16.2 g of compound (B2) was obtained by adding a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, i representing the average polymerization degree is 5.4).
[0333] The obtained compound (B2) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0334] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.42-4.24 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0335] 19 F-NMR (acetone-d6): δ [ppm] = -78.57 (4F), -88.92 to -89.57 (21.6F)
[0336] [Example 14]
[0337] The compound (B2) represented by the above formula (B2) was obtained by the method shown below (in the formula (B2), nb2 representing the average degree of polymerization was 9.7).
[0338] Instead of HOCH2CF2O (CF2CF2O) in Example 10 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. i The same operation as in Example 10 was carried out except that 16.1 g of compound (B2) was obtained by adding a fluoropolyether (number average molecular weight 1300, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, i representing the average polymerization degree is 9.7).
[0339] The obtained compound (B2) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0340] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.42-4.24 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0341] 19 F-NMR (acetone-d6): δ [ppm] = -78.57 (4F), -88.92 to -89.57 (38.8F)
[0342] [Example 15]
[0343] The compound (B2) represented by the above formula (B2) was obtained by the method shown below (in the formula (B2), nb2 representing the average degree of polymerization was 12.3).
[0344] Instead of HOCH2CF2O (CF2CF2O) in Example 10 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. iThe same operation as in Example 10 was carried out except that 16.7 g of compound (B2) was obtained by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, i representing the average polymerization degree is 12.3).
[0345] The obtained compound (B2) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0346] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.42-4.24 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0347] 19 F-NMR (acetone-d6): δ [ppm] = -78.57 (4F), -88.92 to -89.57 (49.2F)
[0348] [Example 16]
[0349] The compound (B3) represented by the above formula (B3) was obtained by the method shown below (in the formula (B3), nb3 representing the average degree of polymerization was 3.1).
[0350] Instead of HOCH2CF2O (CF2CF2O) in Example 10 g (CF2O) h A fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g representing the average degree of polymerization is 3.4, and h representing the average degree of polymerization is 3.4) was used, while HOCH2CF2CF2O (CF2CF2CF2O) was used. j The same operation as in Example 10 was carried out except that 14.6 g of compound (B3) was obtained by adding fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) (40.0 g) represented by CF2CF2CH2OH (wherein j representing the average polymerization degree is 3.1).
[0351] The obtained compound (B3) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0352] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.38-4.19 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0353] 19 F-NMR (acetone-d6): δ [ppm] = -84.22 (12.4F), -86.40 (4F), -124.30 (4F), -130.08 (6.2F)
[0354] [Example 17]
[0355] The compound (B3) represented by the above formula (B3) was obtained by the method shown below (in the formula (B3), nb3 representing the average degree of polymerization was 6.2).
[0356] Instead of HOCH2CF2O (CF2CF2O) in Example 10 g (CF2O) h A fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g representing the average degree of polymerization is 3.4, and h representing the average degree of polymerization is 3.4) was used, while HOCH2CF2CF2O (CF2CF2CF2O) was used. j The same operation as in Example 10 was carried out except that 15.2 g of compound (B3) was obtained by adding fluoropolyether (number average molecular weight 1300, molecular weight distribution 1.1) (40.0 g) represented by CF2CF2CH2OH (wherein j representing the average polymerization degree is 6.2).
[0357] The obtained compound (B3) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0358] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.38-4.19 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0359] 19 F-NMR (acetone-d6): δ [ppm] = -84.22 (24.8F), -86.40 (4F), -124.30 (4F), -130.08 (12.4F)
[0360] [Example 18]
[0361] The compound (B3) represented by the above formula (B3) was obtained by the method shown below (in the formula (B3), nb3 representing the average degree of polymerization is 8).
[0362] Instead of HOCH2CF2O (CF2CF2O) in Example 10g (CF2O) h A fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g representing the average degree of polymerization is 3.4, and h representing the average degree of polymerization is 3.4) was used, while HOCH2CF2CF2O (CF2CF2CF2O) was used. j The same operation as in Example 10 was carried out except that 12.5 g of compound (B3) was obtained by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CF2CH2OH (wherein j representing the average polymerization degree is 8).
[0363] The obtained compound (B3) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0364] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.38-4.19 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0365] 19 F-NMR (acetone-d6): δ [ppm] = -84.22 (32F), -86.40 (4F), -124.30 (4F), -130.08 (16F)
[0366] [Example 19]
[0367] The compound (C1) represented by the above formula (C1) was obtained by the method shown below (in the formula (C1), mc1 representing the average degree of polymerization was 3.4, and nc1 representing the average degree of polymerization was 3.4).
[0368] First, a compound represented by the following formula (16) was synthesized by the method shown below: 2-(4-chlorobutoxy)tetrahydropyran was reacted with the compound (11) shown in Example 1, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize the compound (16) represented by the following formula (16).
[0369]
[0370] 16.9 g of compound (C1) was obtained by the same procedures as in Example 10 except that compound (16) (7.67 g) represented by formula (16) was used instead of compound (12) represented by formula (12) used in Example 10.
[0371] The obtained compound (C1) is subjected to1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0372] 1 H-NMR (acetone-d6): δ [ppm] = 1.68-1.75 (4H), 3.40-4.20 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0373] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0374] [Example 20]
[0375] The compound (C1) represented by the above formula (C1) was obtained by the method shown below (in the formula (C1), mc1 representing the average degree of polymerization was 7.8, and nc1 representing the average degree of polymerization was 7.8).
[0376] Instead of HOCH2CF2O (CF2CF2O) in Example 19 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h The same operation as in Example 19 was performed to obtain 16.5 g of compound (C1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 7.8, and h representing the average polymerization degree is 7.8).
[0377] The obtained compound (C1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0378] 1 H-NMR (acetone-d6): δ [ppm] = 1.68-1.75 (4H), 3.40-4.20 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0379] 19F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0380] [Example 21]
[0381] The compound (D1) represented by the above formula (D1) was obtained by the method shown below (in the formula (D1), md1 representing the average degree of polymerization was 3.4, and nd1 representing the average degree of polymerization was 3.4).
[0382] First, a compound (17) represented by the following formula (17) was synthesized by the method shown below: 2-(6-chlorohexyloxy)tetrahydropyran was reacted with the compound (11) shown in Example 1, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize a compound (17) represented by the following formula (17).
[0383]
[0384] 17.3 g of compound (D1) was obtained by the same procedures as in Example 10 except that compound (17) (8.28 g) represented by formula (17) was used instead of compound (12) represented by formula (12) used in Example 10.
[0385] The obtained compound (D1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0386] 1 H-NMR (acetone-d6): δ [ppm] = 1.46-1.62 (8H), 3.40-4.20 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0387] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0388] [Example 22]
[0389] The compound (D1) represented by the above formula (D1) was obtained by the method shown below (in the formula (D1), md1 representing the average degree of polymerization was 7.8, and nd1 representing the average degree of polymerization was 7.8).
[0390] Instead of HOCH2CF2O (CF2CF2O) in Example 21 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h The same operation as in Example 21 was performed to obtain 17.8 g of compound (D1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 7.8, and h representing the average polymerization degree is 7.8).
[0391] The obtained compound (D1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0392] 1 H-NMR (acetone-d6): δ [ppm] = 1.46-1.62 (8H), 3.40-4.20 (35H), 5.10 (1H), 5.25 (1H), 5.91 (1H)
[0393] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0394] [Example 23]
[0395] The compound (E1) represented by the above formula (E1) was obtained by the method shown below (in the formula (E1), me1 representing the average degree of polymerization was 3.4, and ne1 representing the average degree of polymerization was 3.4).
[0396] First, a compound (19) represented by the following formula (19) is synthesized by the method shown below. After reacting epibromohydrin with 3-butene-1-ol, the epoxy group is hydrolyzed under acidic conditions to synthesize a compound (18) represented by the following formula (18). After the primary hydroxyl group of the obtained compound (18) is protected with a tert-butyldimethylsilyl group, the secondary hydroxyl group is protected with a methoxymethyl group, and the tert-butyldimethylsilyl group is removed from the obtained compound. Finally, epibromohydrin is reacted with the generated primary hydroxyl group to synthesize a compound (19) represented by the following formula (19).
[0397]
[0398] The same procedures as in Example 1 were carried out except that the compound (19) (7.39 g) represented by the formula (19) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 16.9 g of the compound (E1).
[0399] The obtained compound (E1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0400] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 2.34 (2H), 3.40-4.20 (35H), 4.98 (1H), 5.05 (1H), 5.82 (1H)
[0401] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0402] [Example 24]
[0403] The compound (E1) represented by the above formula (E1) was obtained by the method shown below (in the formula (E1), me1 representing the average degree of polymerization was 7.8, and ne1 representing the average degree of polymerization was 7.8).
[0404] Instead of HOCH2CF2O (CF2CF2O) in Example 23 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h The same operation as in Example 23 was performed to obtain 15.7 g of compound (E1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average degree of polymerization is 7.8, and h representing the average degree of polymerization is 7.8).
[0405] The obtained compound (E1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0406] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 2.34 (2H), 3.40-4.20 (35H), 4.98 (1H), 5.05 (1H), 5.82 (1H)
[0407] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0408] [Example 25]
[0409] The compound (F1) represented by the above formula (F1) was obtained by the method shown below (in the formula (F1), mf1 representing the average degree of polymerization was 3.4, and nf1 representing the average degree of polymerization was 3.4).
[0410] First, a compound (21) represented by the following formula (21) is synthesized by the method shown below. After reacting epibromohydrin with 4-penten-1-ol, the epoxy group is hydrolyzed under acidic conditions to synthesize a compound (20) represented by the following formula (20). After the primary hydroxyl group of the obtained compound (20) is protected with a tert-butyldimethylsilyl group, the secondary hydroxyl group is protected with a methoxymethyl group, and the tert-butyldimethylsilyl group is removed from the obtained compound. Finally, epibromohydrin is reacted with the generated primary hydroxyl group to synthesize a compound (21) represented by the following formula (21).
[0411]
[0412] The same procedures as in Example 1 were carried out except that the compound (21) (7.81 g) represented by the formula (21) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 17.1 g of the compound (F1).
[0413] The obtained compound (F1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0414] 1 H-NMR (acetone-d6): δ [ppm] = 1.67 (2H), 1.75 (2H), 2.15 (2H), 3.40-4.20 (35H), 4.97 (1H), 5.03 (1H), 5.82 (1H)
[0415] 19F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0416] [Example 26]
[0417] The compound (F1) represented by the above formula (F1) was obtained by the method shown below (in the formula (F1), mf1 representing the average degree of polymerization was 7.8, and nf1 representing the average degree of polymerization was 7.8).
[0418] Instead of HOCH2CF2O (CF2CF2O) in Example 25 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h The same operation as in Example 25 was performed to obtain 17.7 g of compound (F1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 7.8, and h representing the average polymerization degree is 7.8).
[0419] The obtained compound (F1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0420] 1 H-NMR (acetone-d6): δ [ppm] = 1.67 (2H), 1.75 (2H), 2.15 (2H), 3.40-4.20 (35H), 4.97 (1H), 5.03 (1H), 5.82 (1H)
[0421] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0422] [Example 27]
[0423] The compound (G1) represented by the above formula (G1) was obtained by the method shown below (in the formula (G1), mg1 representing the average degree of polymerization was 3.4, and ng1 representing the average degree of polymerization was 3.4).
[0424] First, a compound (23) represented by the following formula (23) is synthesized by the method shown below. Epibromohydrin is reacted with propargyl alcohol, and then the epoxy group is hydrolyzed under acidic conditions to synthesize a compound (22) represented by the following formula (22). The primary hydroxyl group of the obtained compound (22) is protected with a tert-butyldimethylsilyl group, and then the secondary hydroxyl group is protected with a methoxymethyl group, and the tert-butyldimethylsilyl group is removed from the obtained compound. Finally, epibromohydrin is reacted with the generated primary hydroxyl group to synthesize a compound (23) represented by the following formula (23).
[0425]
[0426] 16.7 g of compound (G1) was obtained by the same operation as in Example 1 except that compound (23) (6.91 g) represented by formula (23) was used instead of compound (10) represented by formula (10) used in Example 1.
[0427] The obtained compound (G1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0428] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 2.48 (1H), 3.40-4.20 (35H)
[0429] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0430] [Example 28]
[0431] The compound (G1) represented by the above formula (G1) was obtained by the method shown below (in the formula (G1), mg1 representing the average degree of polymerization was 7.8, and ng1 representing the average degree of polymerization was 7.8).
[0432] Instead of HOCH2CF2O (CF2CF2O) in Example 27 g (CF2O) hCF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h The same operation as in Example 27 was performed to obtain 16.2 g of compound (G1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 7.8, and h representing the average polymerization degree is 7.8).
[0433] The obtained compound (G1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0434] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 2.48 (1H), 3.40-4.20 (35H)
[0435] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0436] [Example 29]
[0437] The compound (H1) represented by the above formula (H1) was obtained by the method shown below (in the formula (H1), mh1 representing the average degree of polymerization was 3.4, and nh1 representing the average degree of polymerization was 3.4).
[0438] First, a compound (25) represented by the following formula (25) is synthesized by the method shown below. After reacting epibromohydrin with 4-pentyn-1-ol, the epoxy group is hydrolyzed under acidic conditions to synthesize a compound (24) represented by the following formula (24). After the primary hydroxyl group of the obtained compound (24) is protected with a tert-butyldimethylsilyl group, the secondary hydroxyl group is protected with a methoxymethyl group, and the tert-butyldimethylsilyl group is removed from the obtained compound. Finally, epibromohydrin is reacted with the generated primary hydroxyl group to synthesize a compound (25) represented by the following formula (25).
[0439]
[0440] The same procedures as in Example 1 were carried out except that the compound (25) (7.75 g) represented by the formula (25) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 17.1 g of the compound (H1).
[0441] The obtained compound (H1) is 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0442] 1 H-NMR (acetone-d6): δ [ppm] = 1.75-1.78 (4H), 2.00 (1H), 2.30 (2H), 3.40-4.20 (35H)
[0443] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0444] [Example 30]
[0445] The compound (H1) represented by the above formula (H1) was obtained by the method shown below (in the formula (H1), mh1 representing the average degree of polymerization was 7.8, and nh1 representing the average degree of polymerization was 7.8).
[0446] Instead of HOCH2CF2O (CF2CF2O) in Example 29 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h The same operation as in Example 29 was performed to obtain 16.5 g of compound (H1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 7.8, and h representing the average polymerization degree is 7.8).
[0447] The obtained compound (H1) is 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0448] 1H-NMR (acetone-d6): δ [ppm] = 1.75-1.78 (4H), 2.00 (1H), 2.30 (2H), 3.40-4.20 (35H)
[0449] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0450] [Example 31]
[0451] The compound (I1) represented by the above formula (I1) was obtained by the method shown below (in the formula (I1), mi1 representing the average degree of polymerization is 3.4, and ni1 representing the average degree of polymerization is 3.4).
[0452] First, a compound (27) represented by the following formula (27) is synthesized by the method shown below. After reacting epibromohydrin with 2-thiopheneethanol, the epoxy group is hydrolyzed under acidic conditions to synthesize a compound (26) represented by the following formula (26). After the primary hydroxyl group of the obtained compound (26) is protected with a tert-butyldimethylsilyl group, the secondary hydroxyl group is protected with a methoxymethyl group, and the tert-butyldimethylsilyl group is removed from the obtained compound. Finally, epibromohydrin is reacted with the generated primary hydroxyl group to synthesize a compound (27) represented by the following formula (27).
[0453]
[0454] The same procedures as in Example 1 were carried out except that the compound (27) (9.07 g) represented by the formula (27) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 17.7 g of the compound (I1).
[0455] The obtained compound (I1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0456] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.07 (2H), 3.40-4.20 (35H), 6.90 (2H), 7.23 (1H)
[0457] 19F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0458] [Example 32]
[0459] The compound (I1) represented by the above formula (I1) was obtained by the method shown below (in the formula (I1), mi1 representing the average degree of polymerization is 7.8, and ni1 representing the average degree of polymerization is 7.8).
[0460] Instead of HOCH2CF2O (CF2CF2O) in Example 31 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h The same operation as in Example 31 was performed to obtain 15.4 g of compound (I1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average degree of polymerization is 7.8, and h representing the average degree of polymerization is 7.8).
[0461] The obtained compound (I1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0462] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.07 (2H), 3.40-4.20 (35H), 6.90 (2H), 7.23 (1H)
[0463] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0464] [Example 33]
[0465] The compound (J1) represented by the above formula (J1) was obtained by the method shown below (in the formula (J1), mj1 representing the average degree of polymerization was 3.4, and nj1 representing the average degree of polymerization was 3.4).
[0466] First, a compound (29) represented by the following formula (29) is synthesized by the method shown below. After reacting epibromohydrin with 1-methylpyrazole-5-methanol, the epoxy group is hydrolyzed under acidic conditions to synthesize a compound (28) represented by the following formula (28). After the primary hydroxyl group of the obtained compound (28) is protected with a tert-butyldimethylsilyl group, the secondary hydroxyl group is protected with a methoxymethyl group, and the tert-butyldimethylsilyl group is removed from the obtained compound. Finally, epibromohydrin is reacted with the generated primary hydroxyl group to synthesize a compound (29) represented by the following formula (29).
[0467]
[0468] The same procedures as in Example 1 were carried out except that the compound (29) (8.59 g) represented by the formula (29) was used instead of the compound (10) represented by the formula (10) used in Example 1, to obtain 17.5 g of the compound (J1).
[0469] The obtained compound (J1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0470] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (38H), 6.20 (1H), 7.31 (1H)
[0471] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0472] [Example 34]
[0473] The compound (J1) represented by the above formula (J1) was obtained by the method shown below (in the formula (J1), mj1 representing the average degree of polymerization was 7.8, and nj1 representing the average degree of polymerization was 7.8).
[0474] Instead of HOCH2CF2O (CF2CF2O) in Example 33 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O)h The same operation as in Example 33 was performed to obtain 15.8 g of compound (J1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 7.8, and h representing the average polymerization degree is 7.8).
[0475] The obtained compound (J1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0476] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (38H), 6.20 (1H), 7.31 (1H)
[0477] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0478] [Example 35]
[0479] The compound (K1) represented by the above formula (K1) was obtained by the method shown below (in the formula (K1), mk1 representing the average degree of polymerization was 3.4, and nk1 representing the average degree of polymerization was 3.4).
[0480] First, a compound (30) represented by the following formula (30) was synthesized by the method shown below: 4-methoxyphenol and allyl glycidyl ether were reacted, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize a compound (30) represented by the following formula (30).
[0481]
[0482] The same procedures as in Example 1 were carried out except that the compound (30) (7.63 g) represented by the formula (30) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 17.7 g of the compound (K1).
[0483] The obtained compound (K1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0484] 1H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (36H), 6.85 (4H)
[0485] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0486] [Example 36]
[0487] The compound (K1) represented by the above formula (K1) was obtained by the method shown below (in the formula (K1), mk1 representing the average degree of polymerization was 7.8, and nk1 representing the average degree of polymerization was 7.8).
[0488] Instead of HOCH2CF2O (CF2CF2O) in Example 35 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h A fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average degree of polymerization is 7.8, and h representing the average degree of polymerization is 7.8) was added. Except for this, the same operation as in Example 35 was carried out to obtain 16.1 g of compound (K1).
[0489] The obtained compound (K1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0490] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (36H), 6.85 (4H)
[0491] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0492] [Example 37]
[0493] The compound (L1) represented by the above formula (L1) was obtained by the method shown below (in the formula (L1), ml1 indicating the average degree of polymerization was 3.4, and nl1 indicating the average degree of polymerization was 3.4).
[0494] First, a compound (31) represented by the following formula (31) was synthesized by the method shown below: 3-Cyanophenol and allyl glycidyl ether were reacted, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize a compound (31) represented by the following formula (31).
[0495]
[0496] The same procedures as in Example 1 were carried out except that the compound (31) (7.48 g) represented by the formula (31) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 17.6 g of the compound (L1).
[0497] The obtained compound (L1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0498] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (33H), 7.28-7.34 (3H), 7.50 (1H)
[0499] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0500] [Example 38]
[0501] The compound (L1) represented by the above formula (L1) was obtained by the method shown below (in the formula (L1), ml1 indicating the average degree of polymerization was 7.8, and nl1 indicating the average degree of polymerization was 7.8).
[0502] Instead of HOCH2CF2O (CF2CF2O) in Example 37 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) hThe same operation as in Example 37 was performed to obtain 15.2 g of compound (L1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 7.8, and h representing the average polymerization degree is 7.8).
[0503] The obtained compound (L1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0504] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (33H), 7.28-7.34 (3H), 7.50 (1H)
[0505] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0506] [Example 39]
[0507] The compound (M1) represented by the above formula (M1) was obtained by the method shown below (in the formula (M1), mm1 representing the average degree of polymerization was 3.4, and nm1 representing the average degree of polymerization was 3.4).
[0508] First, a compound (33) represented by the following formula (33) is synthesized by the method shown below. After reacting epibromohydrin with 3-cyanopropanol, the epoxy group is hydrolyzed under acidic conditions to synthesize a compound (32) represented by the following formula (32). After the primary hydroxyl group of the obtained compound (32) is protected with a tert-butyldimethylsilyl group, the secondary hydroxyl group is protected with a methoxymethyl group, and the tert-butyldimethylsilyl group is removed from the obtained compound. Finally, epibromohydrin is reacted with the generated primary hydroxyl group to synthesize a compound (33) represented by the following formula (33).
[0509]
[0510] The same procedures as in Example 1 were carried out except that the compound (33) (7.78 g) represented by the formula (33) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 17.1 g of the compound (M1).
[0511] The obtained compound (M1) is 1 H-NMR and 19The structure was identified by the following results from F-NMR measurement.
[0512] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 1.88 (2H), 2.54 (2H), 3.40-4.20 (35H)
[0513] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0514] [Example 40]
[0515] The compound (M1) represented by the above formula (M1) was obtained by the method shown below (in the formula (M1), mm1 representing the average degree of polymerization is 7.8, and nm1 representing the average degree of polymerization is 7.8).
[0516] Instead of HOCH2CF2O (CF2CF2O) in Example 39 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h A fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average degree of polymerization is 7.8, and h representing the average degree of polymerization is 7.8) was added. Except for this, the same operation as in Example 39 was carried out to obtain 16.2 g of compound (M1).
[0517] The obtained compound (M1) is 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0518] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 1.88 (2H), 2.54 (2H), 3.40-4.20 (35H)
[0519] 19F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0520] [Example 41]
[0521] The compound (N1) represented by the above formula (N1) was obtained by the method shown below (in the formula (N1), mn1 representing the average degree of polymerization was 3.4, and nn1 representing the average degree of polymerization was 3.4).
[0522] First, a compound (35) represented by the following formula (35) is synthesized by the method shown below. Epibromohydrin is reacted with 4-cyanobutanol, and then the epoxy group is hydrolyzed under acidic conditions to synthesize a compound (34) represented by the following formula (34). The primary hydroxyl group of the obtained compound (34) is protected with a tert-butyldimethylsilyl group, and then the secondary hydroxyl group is protected with a methoxymethyl group, and the tert-butyldimethylsilyl group is removed from the obtained compound. Finally, epibromohydrin is reacted with the generated primary hydroxyl group to synthesize a compound (35) represented by the following formula (35).
[0523]
[0524] The same procedures as in Example 1 were carried out except that the compound (35) (8.20 g) represented by the formula (35) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 17.3 g of the compound (N1).
[0525] The obtained compound (N1) is 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0526] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (6H), 2.54 (2H), 3.40-4.20 (35H)
[0527] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0528] [Example 42]
[0529] The compound (N1) represented by the above formula (N1) was obtained by the method shown below (in the formula (N1), mn1 representing the average degree of polymerization was 7.8, and nn1 representing the average degree of polymerization was 7.8).
[0530] Instead of HOCH2CF2O (CF2CF2O) in Example 41 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h A fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average degree of polymerization is 7.8, and h representing the average degree of polymerization is 7.8) was added. Except for this, the same operation as in Example 41 was carried out to obtain 15.4 g of compound (N1).
[0531] The obtained compound (N1) is 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0532] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (6H), 2.54 (2H), 3.40-4.20 (35H)
[0533] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0534] [Example 43]
[0535] The compound (O1) represented by the above formula (O1) was obtained by the method shown below (in the formula (O1), mo1 representing the average degree of polymerization is 3.4, and no1 representing the average degree of polymerization is 3.4).
[0536] First, a compound (36) represented by the following formula (36) is synthesized by the method shown below. The primary hydroxyl group of 3-methoxy-1,2-propanediol is protected with a tert-butyldimethylsilyl group, and then the secondary hydroxyl group is protected with a methoxymethyl group, and the tert-butyldimethylsilyl group is removed from the obtained compound. Finally, epibromohydrin is reacted with the generated primary hydroxyl group to synthesize a compound (36) represented by the following formula (36).
[0537]
[0538] The same procedures as in Example 1 were carried out except that the compound (36) (6.19 g) represented by the formula (36) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 16.4 g of the compound (O1).
[0539] The obtained compound (O1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0540] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (36H)
[0541] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0542] [Example 44]
[0543] The compound (O1) represented by the above formula (O1) was obtained by the method shown below (in the formula (O1), mo1 representing the average degree of polymerization is 7.8, and no1 representing the average degree of polymerization is 7.8).
[0544] Instead of HOCH2CF2O (CF2CF2O) in Example 43 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h The same operation as in Example 43 was performed to obtain 16.1 g of compound (O1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 7.8, and h representing the average polymerization degree is 7.8).
[0545] The obtained compound (O1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0546] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (36H)
[0547] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0548] [Example 45]
[0549] The compound (P1) represented by the above formula (P1) was obtained by the method shown below (in the formula (P1), mp1 representing the average degree of polymerization was 3.4, and np1 representing the average degree of polymerization was 3.4).
[0550] First, a compound (37) represented by the following formula (37) was synthesized by the following method: Compound (11) described in Example 1 was reacted with bromopropane, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize a compound (37) represented by the following formula (37).
[0551]
[0552] The same procedures as in Example 1 were carried out except that the compound (37) (7.03 g) represented by the formula (37) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 16.8 g of the compound (P1).
[0553] The obtained compound (P1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0554] 1 H-NMR (acetone-d6): δ [ppm] = 0.84 (3H), 1.55 (2H), 1.75 (2H), 3.40-4.20 (35H)
[0555] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0556] [Example 46]
[0557] The compound (P1) represented by the above formula (P1) was obtained by the method shown below (in the formula (P1), mp1 representing the average degree of polymerization was 7.8, and np1 representing the average degree of polymerization was 7.8).
[0558] Instead of HOCH2CF2O (CF2CF2O) in Example 45 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h The same operation as in Example 45 was performed to obtain 14.4 g of compound (P1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 7.8, and h representing the average polymerization degree is 7.8).
[0559] The obtained compound (P1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0560] 1 H-NMR (acetone-d6): δ [ppm] = 0.84 (3H), 1.55 (2H), 1.75 (2H), 3.40-4.20 (35H)
[0561] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0562] [Example 47]
[0563] The compound (Q1) represented by the above formula (Q1) was obtained by the method shown below (in the formula (Q1), mq1 representing the average degree of polymerization was 3.4, and nq1 representing the average degree of polymerization was 3.4).
[0564] First, a compound (38) represented by the following formula (38) was synthesized by the following method: 2,2,2-trifluoroethanol and allyl glycidyl ether were reacted, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize a compound (38) represented by the following formula (38).
[0565]
[0566] The same procedures as in Example 1 were carried out except that the compound (38) (6.91 g) represented by the formula (38) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 17.3 g of the compound (Q1).
[0567] The obtained compound (Q1) is 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0568] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (35H)
[0569] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -75.22 (3F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0570] [Example 48]
[0571] The compound (Q1) represented by the above formula (Q1) was obtained by the method shown below (in the formula (Q1), mq1 representing the average degree of polymerization was 7.8, and nq1 representing the average degree of polymerization was 7.8).
[0572] Instead of HOCH2CF2O (CF2CF2O) in Example 47 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h A fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average degree of polymerization is 7.8, and h representing the average degree of polymerization is 7.8) was added. Except for this, the same operation as in Example 47 was carried out to obtain 16.3 g of compound (Q1).
[0573] The obtained compound (Q1) is 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0574] 1H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (35H)
[0575] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -75.22 (3F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0576] [Example 49]
[0577] The compound (R1) represented by the above formula (R1) was obtained by the method shown below (in the formula (R1), mr1 representing the average degree of polymerization was 3.4, and nr1 representing the average degree of polymerization was 3.4).
[0578] First, a compound (39) represented by the following formula (39) is synthesized by the following method: 2,2,3,3,3-pentafluoro-1-propanol is reacted with allyl glycidyl ether, and then the double bond is oxidized using m-chloroperbenzoic acid to synthesize a compound (39) represented by the following formula (39).
[0579]
[0580] The same procedures as in Example 1 were carried out except that the compound (39) (8.41 g) represented by the formula (39) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 18.0 g of the compound (R1).
[0581] The obtained compound (R1) is 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0582] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (35H)
[0583] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -84.40 (3F), -89.16 to -91.14 (13.6F), -124.36 (2F)
[0584] [Example 50]
[0585] The compound (R1) represented by the above formula (R1) was obtained by the method shown below (in the formula (R1), mr1 representing the average degree of polymerization was 7.8, and nr1 representing the average degree of polymerization was 7.8).
[0586] Instead of HOCH2CF2O (CF2CF2O) in Example 49 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h The same operation as in Example 49 was performed to obtain 15.7 g of compound (R1) by adding a fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average polymerization degree is 7.8, and h representing the average polymerization degree is 7.8).
[0587] The obtained compound (R1) is 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0588] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (35H)
[0589] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -84.40 (3F), -89.16 to -91.14 (31.2F), -124.36 (2F)
[0590] [Example 51]
[0591] The compound (S1) represented by the above formula (S1) was obtained by the method shown below (in the formula (S1), ms1 representing the average degree of polymerization was 3.4, and ns1 representing the average degree of polymerization was 3.4).
[0592] First, a compound (40) represented by the following formula (40) was synthesized by the following method: 2-bromoethyl methyl ether was reacted with the compound (11) shown in Example 1, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize a compound (40) represented by the following formula (40).
[0593]
[0594] The same procedures as in Example 1 were carried out except that the compound (40) (7.51 g) represented by the formula (40) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 17.6 g of the compound (S1).
[0595] The obtained compound (S1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0596] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.31 (3H), 3.40-4.20 (37H)
[0597] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0598] [Example 52]
[0599] The compound (S1) represented by the above formula (S1) was obtained by the method shown below (in the formula (S1), ms1 representing the average degree of polymerization was 7.8, and ns1 representing the average degree of polymerization was 7.8).
[0600] Instead of HOCH2CF2O (CF2CF2O) in Example 51 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h A fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average degree of polymerization is 7.8, and h representing the average degree of polymerization is 7.8) was added. Except for this, the same operation as in Example 51 was carried out to obtain 16.1 g of compound (S1).
[0601] The obtained compound (S1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0602] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.31 (3H), 3.40-4.20 (37H)
[0603] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0604] [Example 53]
[0605] The compound (T1) represented by the above formula (T1) was obtained by the method shown below (in the formula (T1), mt1 representing the average degree of polymerization was 3.4, and nt1 representing the average degree of polymerization was 3.4).
[0606] First, a compound (42) represented by the following formula (42) is synthesized by the method shown below. After reacting epibromohydrin with ethylene glycol monoallyl ether, the epoxy group is hydrolyzed under acidic conditions to synthesize a compound (41) represented by the following formula (41). The primary hydroxyl group of the obtained compound (41) is protected with a tert-butyldimethylsilyl group, and then the secondary hydroxyl group is protected with a methoxymethyl group, and the tert-butyldimethylsilyl group is removed from the obtained compound. Finally, epibromohydrin is reacted with the generated primary hydroxyl group to synthesize a compound (42) represented by the following formula (42).
[0607]
[0608] The same procedures as in Example 1 were carried out except that the compound (42) (8.29 g) represented by the formula (42) was used instead of the compound (10) represented by the formula (10) used in Example 1, thereby obtaining 17.3 g of the compound (T1).
[0609] The obtained compound (T1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0610] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (39H), 5.10 (1H), 5.26 (1H), 5.91 (1H)
[0611] 19F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (6.8F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (13.6F)
[0612] [Example 54]
[0613] The compound (T1) represented by the above formula (T1) was obtained by the method shown below (in the formula (T1), mt1 representing the average degree of polymerization was 7.8, and nt1 representing the average degree of polymerization was 7.8).
[0614] Instead of HOCH2CF2O (CF2CF2O) in Example 53 g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4.) was used as a fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1), while HOCH2CF2O (CF2CF2O) was used. g (CF2O) h A fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein, g representing the average degree of polymerization is 7.8, and h representing the average degree of polymerization is 7.8) was added. Except for this, the same operation as in Example 53 was carried out to obtain 16.0 g of compound (T1).
[0615] The obtained compound (T1) is subjected to 1 H-NMR and 19 The structure was identified by the following results from F-NMR measurement.
[0616] 1 H-NMR (acetone-d6): δ [ppm] = 1.75 (2H), 3.40-4.20 (39H), 5.10 (1H), 5.26 (1H), 5.91 (1H)
[0617] 19 F-NMR (acetone-d6): δ [ppm] = -51.99 to -55.72 (15.6F), -78.48 (2F), -80.66 (2F), -89.16 to -91.14 (31.2F)
[0618] [Comparative Examples 1 to 4]
[0619] By the method described in Patent Document 5, a compound (AA) represented by the following formula (AA) was synthesized.
[0620]
[0621] (In formula (AA), maa and naa indicating the average degree of polymerization are both 3.4 in Comparative Example 1, 6.2 in Comparative Example 2, 7.8 in Comparative Example 3, and 10 in Comparative Example 4.)
[0622] [Comparative Examples 5 to 8]
[0623] By the method described in Patent Document 4, a compound (BB) represented by the following formula (BB) was synthesized.
[0624]
[0625] (In formula (BB), mbb and nbb indicating the average degree of polymerization are both 3.4 in Comparative Example 5, 6.2 in Comparative Example 6, 7.8 in Comparative Example 7, and 10 in Comparative Example 8.)
[0626] [Comparative Example 9, Comparative Example 10]
[0627] By the method described in Patent Document 7, a compound (CC) represented by the following formula (CC) was synthesized.
[0628]
[0629] (In formula (CC), mcc and ncc indicating the average degree of polymerization are both 3.4 in Comparative Example 9 and 7.8 in Comparative Example 10.)
[0630] [Comparative Example 11, Comparative Example 12]
[0631] By the method described in Patent Document 7, a compound (DD) represented by the following formula (DD) was synthesized.
[0632]
[0633] (In formula (DD), mdd and ndd indicating the average degree of polymerization are both 3.4 in Comparative Example 11, and 7.8 in Comparative Example 12.)
[0634] [Comparative Example 13, Comparative Example 14]
[0635] By the method described in Patent Document 6, a compound (EE) represented by the following formula (EE) was synthesized.
[0636]
[0637] (In formula (EE), mee and nee indicating the average degree of polymerization are both 3.4 in Comparative Example 13, and both mee and nee are 7.8 in Comparative Example 14.)
[0638] When the compounds obtained in Examples 1 to 54 and Comparative Examples 1 to 14 are substituted into the formula (1), R 1 ~R 3 、(O(CH2) a ) b The structures of [A], [B] and [C] are shown in Table 1 below.
[0639] [Table 1]
[0640] Table 1
[0641]
[0642] ※1: Replace R 3 ,-O-CH2-CH(OH)-CH2-O-CH2-CH2-OH
[0643] ※2: Replace R 3 ,-O-CH2-CH(OH)-CH2-O-CH2-CH2-CH2-OH
[0644] Next, a lubricant layer forming solution was prepared by the method described below using the compounds obtained in Examples 1 to 54 and Comparative Examples 1 to 14. Furthermore, the lubricant layer of a magnetic recording medium was formed by the method described below using the obtained lubricant layer forming solution, thereby obtaining magnetic recording media of Examples 1 to 54 and Comparative Examples 1 to 14.
[0645] [Lubricating layer forming solution]
[0646] The compounds obtained in Examples 1 to 54 and Comparative Examples 1 to 14 were dissolved in a fluorine-based solvent, Batorel (registered trademark) XF (trade name, manufactured by Mitsui Dupont Fluoro Chemical Co., Ltd.), respectively, to form a film with a thickness of 100 μm when applied on the protective layer. The solution was diluted with Batler XF in a manner of 0.001 mass % to 0.01 mass % to prepare a lubricating layer forming solution having a compound concentration of 0.001 mass % to 0.01 mass %.
[0647] [Magnetic recording media]
[0648] A magnetic recording medium was prepared in which an adhesion layer, a soft magnetic layer, a first base layer, a second base layer, a magnetic layer, and a protective layer were sequentially provided on a substrate having a diameter of 65 mm. The protective layer was formed of carbon nitride. On the protective layer of the magnetic recording medium in which each layer up to the protective layer was formed, the lubricating layer forming solution of Examples 1 to 54 and Comparative Examples 1 to 14 was applied by a dipping method.
[0649] Then, the magnetic recording medium coated with the lubricating layer forming solution was placed in a thermostatic bath at 120° C. and subjected to a heat treatment for 10 minutes. Thus, a lubricating layer was formed on the protective layer, and a magnetic recording medium was obtained.
[0650] The magnetic recording media of Examples 1 to 54 and Comparative Examples 1 to 14 obtained in this manner were evaluated by measuring the film thickness of the lubricating layer, measuring the adhesion (adhesion rate) between the lubricating layer and the protective layer, testing the adhesion characteristics, and testing the peeling characteristics. The results are shown in Tables 2 to 5.
[0651] [Lubricating layer thickness measurement]
[0652] The peak height of the CF vibration expansion of the lubricating layer was measured using FT-IR (trade name: Nicolet iS50, manufactured by Thermo Fisher Scientific). The film thickness of the lubricating layer was calculated from the measured value of the peak height of the CF vibration expansion of the lubricating layer using a correlation formula obtained by the method described below.
[0653] [Calculation method of relevant formula]
[0654] The surface of the magnetic disk is provided with an adhesive layer, a soft magnetic layer, a first base layer, a second base layer, a magnetic layer and a protective layer in sequence on a substrate with a diameter of 65 mm. (Every ) formed a lubricating layer with a film thickness of .
[0655] Then, for each disk with a lubricating layer formed, the film thickness increase compared to the disk surface without a lubricating layer was measured using an ellipsometer, and the film thickness of the lubricating layer was determined. In addition, for each disk with a lubricating layer formed, the peak height in CF vibration expansion was measured using FT-IR.
[0656] Furthermore, a correlation formula between the peak height obtained by FT-IR and the film thickness of the lubricating layer obtained using an ellipsometer was determined.
[0657] [Measurement of Adhesion (Adhesion Ratio) between Lubricating Layer and Protective Layer]
[0658] The magnetic recording medium having a lubricating layer formed thereon was immersed in a solvent, バートレル XF, for 10 minutes and then washed by a pulling method. The speed at which the magnetic recording medium was immersed in the solvent was set to 10 mm / sec, and the speed at which it was pulled was set to 1.2 mm / sec. Then, the film thickness of the lubricating layer was measured by the same method as that of the film thickness of the lubricating layer before washing.
[0659] Furthermore, the film thickness of the lubricating layer before washing is defined as α, and the film thickness of the lubricating layer after washing (after solvent immersion) is defined as β, and the lubricant bonding rate (adhesion rate) is calculated from the ratio of α to β ((β / α)×100(%)). Using the calculated adhesion rate, the adhesion between the lubricating layer and the protective layer was evaluated according to the evaluation criteria shown below.
[0660] The adhesion ratio can be used as an indicator of the bonding strength between the lubricating layer and the protective layer. If the adhesion between the lubricating layer and the protective layer is poor, part of the fluorinated ether compound contained in the lubricating layer will be dissolved into the Batler XF and washed away. Therefore, the film thickness of the lubricating layer after washing becomes smaller and the adhesion ratio decreases.
[0661] "Evaluation criteria for adhesion (adhesion rate)"
[0662] A: Adhesion rate 75% or more
[0663] B: Adhesion rate 70% to 74%
[0664] C: Adhesion rate 50% to 69%
[0665] D: Adhesion rate 49% or less
[0666] [Adhesion characteristics test]
[0667] The magnetic recording medium and the magnetic head were installed on the spin stand, and the magnetic head was floated at a fixed point for 10 minutes under normal temperature and reduced pressure (about 250 Torr). Then, the surface of the magnetic head opposite to the magnetic recording medium was analyzed using an ESCA (Electron Spectroscopy for Chemical Analysis) analysis device. The intensity (signal intensity (au)) of the peak derived from fluorine obtained by ESCA analysis represents the amount of lubricant attached to the magnetic head. Using the obtained signal intensity, the adhesion characteristics were evaluated by the evaluation criteria shown below.
[0668] "Evaluation criteria for adhesion properties"
[0669] A: Signal strength below 160 (very little adhesion)
[0670] B: Signal strength 161~300 (small amount of adhesion)
[0671] C: Signal strength 301~1000 (high adhesion)
[0672] D: Signal strength 1001 or more (very high amount of adhesion)
[0673] [Shedding characteristics test]
[0674] The magnetic recording medium was mounted on a spin stand and rotated at a rotation speed of 10,000 rpm for 72 hours in an environment of 80°C. Before and after this operation, the film thickness of the lubricating layer at a position with a radius of 20 mm from the center of the magnetic recording medium was measured by FT-IR, and the film thickness reduction rate of the lubricating layer before and after the test was calculated. Using the calculated film thickness reduction rate, the shedding characteristics were evaluated according to the evaluation criteria shown below.
[0675] "Evaluation criteria for shedding characteristics"
[0676] A: Film thickness reduction rate less than 2%
[0677] B: Film thickness reduction rate is greater than 2% and less than 3%
[0678] C: Film thickness reduction rate is greater than 3% and less than 9%
[0679] D: Film thickness reduction rate more than 10%
[0680] From these results, comprehensive evaluation was performed according to the evaluation criteria shown below.
[0681] “Comprehensive evaluation”
[0682] A: The evaluations of adhesion ratio, adhesive property, and peeling property were all A.
[0683] B: The evaluations of adhesion ratio, adhesive property, and peeling property were A or B, and at least one of them was B.
[0684] C: Among the evaluations of adhesion ratio, adhesive property, and peeling property, at least one was C, and none was D.
[0685] D: At least one of the evaluations of adhesion ratio, adhesive property, and peeling property was rated as D.
[0686] [Table 2]
[0687]
[0688] [Table 3]
[0689]
[0690] [Table 4]
[0691]
[0692] [Table 5]
[0693]
[0694] As shown in Tables 2 to 5, the magnetic recording media of Examples 1 to 54 used the fluorinated ether compound represented by formula (1), and therefore had a higher bonding rate than the magnetic recording media of Comparative Examples 1 to 14, and the adhesion between the lubricating layer and the protective layer was good.
[0695] In addition, as shown in Tables 2 to 5, it is clear that the magnetic recording media of Examples 1 to 54 use the fluorine-containing ether compound represented by formula (1), so the signal intensity derived from fluorine obtained by ESCA analysis is smaller than that of the magnetic recording media of Comparative Examples 1 to 14, which can suppress adhesion.
[0696] In addition, as shown in Tables 2 to 5, it is clear that the magnetic recording media of Examples 1 to 54 use the fluorinated ether compound represented by formula (1), so the film thickness reduction rate is smaller than that of the magnetic recording media of Comparative Examples 1 to 3, 5 to 7, and 9 to 14 with the same number average molecular weight, and can suppress shedding.
[0697] In the magnetic recording media of Comparative Examples 1 to 14, when the comparative examples using the same fluorine-containing ether compound are compared with each other, it is found that the adhesion property and the peeling property are greatly deteriorated as the number average molecular weight decreases.
[0698] On the other hand, in the magnetic recording media of Examples 1 to 54, even when the number average molecular weight was reduced, significant deterioration of the adhesion property and the peeling property was not observed.
[0699] In Comparative Examples 1 to 4, R represented by formula (4) in formula (1) was used. 3 The compound (AA) in which f = 1 was evaluated. Since f = 1 in the compound (AA), the structure is stabilized by the regular arrangement of the five-membered ring-type intramolecular hydrogen bonds between the ether oxygen atom and the hydroxyl group in formula (4), and the adhesion (adhesion rate) to the protective layer is reduced, and a tendency of deterioration of the adhesion and peeling properties is confirmed.
[0700] Furthermore, when Comparative Examples 1 and 2 concerning the compound (AA) are compared with Comparative Examples 3 and 4, it is confirmed that the adhesion and peeling properties tend to deteriorate in Comparative Examples 1 and 2 having a small number average molecular weight.
[0701] In Comparative Examples 5 to 8, R in Formula (1) 3 is replaced by -O-CH2-CH(OH)-CH2-O-CH2-CH2-OH, and has one secondary hydroxyl group and one primary hydroxyl group. That is, R 3Therefore, the adhesion to the protective layer is reduced, and the fluorine-containing ether compound that does not adhere to the protective layer aggregates and is easily attached to the magnetic head as a foreign matter.
[0702] Furthermore, when Comparative Examples 5 and 6 concerning the compound (BB) are compared with Comparative Examples 7 and 8, it is confirmed that the adhesion and peeling properties tend to deteriorate in Comparative Examples 5 and 6 having a small number average molecular weight.
[0703] In Comparative Examples 9 to 12, R represented by formula (4) in formula (1) was used. 3 Evaluation tests were conducted on compounds (CC) and (DD) in which f = 1. Since f = 1 in compounds (CC) and (DD), the five-membered ring-type intramolecular hydrogen bonds between the ether oxygen atom and the hydroxyl group in formula (4) are regularly arranged to stabilize the structure, and the adhesion (adhesion rate) to the protective layer is reduced, confirming a tendency for the adhesion and peeling characteristics to deteriorate.
[0704] In addition, when Comparative Examples 9 and 10 concerning Compound (CC) are compared, the adhesion and peeling properties tend to be deteriorated in Comparative Example 9 having a smaller number average molecular weight. When Comparative Examples 11 and 12 concerning Compound (DD) are compared, the adhesion and peeling properties tend to be deteriorated in Comparative Example 11 having a smaller number average molecular weight.
[0705] In Comparative Examples 13 and 14, the sum of c and d in the -[A]-[B]- structure in Formula (1) is 1, and R in Formula (1) is 3 is replaced by -O-CH2-CH(OH)-CH2-O-CH2-CH2-CH2-OH, and has one secondary hydroxyl group and one primary hydroxyl group. That is, compared with the formula (1) of the present invention, in the -[A]-[B]- structure and in R 3 Therefore, the adhesion to the protective layer is reduced, and the tendency of the adhesion property and the peeling property to deteriorate is confirmed.
[0706] By comparing Examples 1 to 3 (compound (A1)) with Comparative Examples 1 to 4 (compound (AA)), Examples 37 to 38 (compound (L1)) with Comparative Examples 9 to 10 (compound (CC)), and Examples 39 to 40 (compound (M1)) with Comparative Examples 11 to 12 (compound (DD)), it is clear that by comparing R in the fluorinated ether compound represented by formula (1) with 3 The number of methylene carbon atoms is increased by one, thereby greatly improving the bonding rate and the adhesion and peeling properties.
[0707] These results are considered to be because the terminal primary hydroxyl groups of compounds (AA), (CC) and (DD) did not effectively participate in the bonding with the active sites on the protective layer, and thus could not sufficiently obtain adhesion with the protective layer. On the other hand, it is speculated that by replacing R 3 As the number of methylene carbon atoms increases, the regular arrangement of the five-membered ring type by the ether oxygen atoms and the hydroxyl groups in the molecule is disrupted, and the intramolecular interaction of the hydroxyl groups is inhibited. As a result, the adhesion to the protective layer is greatly improved.
[0708] Industrial Availability
[0709] Provided is a fluorine-containing ether compound which can form a lubricating layer having good adhesion to a protective layer and can suppress sticking and peeling even when the molecular weight is reduced and which can be suitably used as a material for a lubricant for a magnetic recording medium.
[0710] Explanation of symbols
[0711] 10···magnetic recording medium, 11···substrate, 12···adhesion layer, 13···soft magnetic layer, 14···first base layer, 15···second base layer, 16···magnetic layer, 17···protective layer, 18···lubricating layer.
Claims
1. A fluorine-containing ether compound, characterized in that It is represented by the following formula (1), and its number average molecular weight is in the range of 1000 to 2300. R 1 -(O(CH2) a ) b -[A]-[B]-O-CH2-R 2 -CH2-R 3 (1) In formula (1), R 1 is any one of an alkyl group having 1 to 6 carbon atoms, an alkyl group having 1 to 6 carbon atoms having a substituent, and an organic group having at least one double bond or triple bond, wherein the substituent is a fluoro group, and the organic group having at least one triple bond is an alkynyl group having 3 to 8 carbon atoms; a is an integer of 2 to 4, and b is 0 or 1; [A] is represented by the following formula (2); c in formula (2) is 1 or 2; [B] is represented by the following formula (3); d in formula (3) is 0 or 1, and e is an integer of 2 to 4; wherein the sum of the values of c in formula (2) and d in formula (3) is 2; R 2 is a perfluoropolyether chain; R 3 It is represented by the following formula (4); in the formula (4), f is an integer from 2 to 5, 2. The fluorinated ether compound according to claim 1, wherein R in the formula (1) 1 It is the aforementioned alkyl group having 1 to 6 carbon atoms.
3. The fluorinated ether compound according to claim 1, wherein R in the formula (1) 1 It is the alkyl group having 1 to 6 carbon atoms which has a substituent.
4. The fluorinated ether compound according to claim 1, wherein R in the formula (1) 1 It is any one of an organic group having 6 to 12 carbon atoms having an aromatic hydrocarbon, an organic group having 3 to 10 carbon atoms having an aromatic heterocycle, an alkenyl group having 2 to 8 carbon atoms, and an alkynyl group having 3 to 8 carbon atoms.
5. The fluorinated ether compound according to claim 1, wherein R in the formula (1) 1 It is one group selected from methyl, ethyl, n-propyl, isopropyl, 2,2,2-trifluoroethyl, 2,2,3,3,3-pentafluoropropyl, 2,2,2,2,2,2-hexafluoroisopropyl, phenyl, methoxyphenyl, phenethyl, thienylethyl, N-methylpyrazolylmethyl, allyl, 3-butenyl, 4-pentenyl, propargyl, 3-butynyl, and 4-pentynyl.
6. The fluorinated ether compound according to claim 1 or 2, wherein R in the formula (1) 2 is any one of the following formulas (5) to (8), -CF2O-(CF2CF2O) g -(CF2O) h -CF2-(5) In formula (5), g and h are average polymerization degrees, g represents 3 to 8, and h represents 3 to 8; -CF2O-(CF2CF2O) i -CF2-(6) i in formula (6) is the average degree of polymerization and represents 5 to 13; -CF2CF2O-(CF2CF2CF2O) j -CF2CF2-(7) j in formula (7) is the average degree of polymerization and represents 3 to 8; -CF(CF3)-(OCF(CF3)CF2) k -OCF(CF3)-(8) In the formula (8), k is an average degree of polymerization and represents 3 to 8.
7. The fluorine-containing ether compound according to claim 1, wherein the compound represented by the formula (1) is any one of the compounds represented by the following formulas (A1) to (A3) and (B1) to (B3), In formula (A1), ma1 and na1 are average polymerization degrees, ma1 represents 3 to 8, and na1 represents 3 to 8; In formula (A2), na2 is the average degree of polymerization and represents 5 to 13; In formula (A3), na3 is the average degree of polymerization and represents 3 to 8; In formula (B1), mb1 and nb1 are average polymerization degrees, mb1 represents 3 to 8, and nb1 represents 3 to 8; In formula (B2), nb2 is the average degree of polymerization and represents 5 to 13; In the formula (B3), nb3 is an average degree of polymerization and represents 3 to 8.
8. A lubricant for a magnetic recording medium, characterized in that: The fluorine-containing ether compound according to any one of claims 1 to 7.
9. A magnetic recording medium, characterized in that: A magnetic recording medium comprising at least a magnetic layer, a protective layer and a lubricating layer provided in this order on a substrate, wherein the lubricating layer comprises the fluorine-containing ether compound according to any one of claims 1 to 7. 10 . The magnetic recording medium according to claim 9 , wherein the lubricating layer has an average film thickness of 0.5 nm to 2.0 nm.
Citation Information
Patent Citations
JP1971032144Y1
Averaging device for reverse projection value
JP1979065454A
Electron gun structure of cathode-ray tube
JP1984009837A
Fluorine-containing ether compound, lubricating agent for magnetic recording media, and magnetic recording medium
WO2017154403A1
Fluorinated ether compound, lubricant for magnetic storage medium, and magnetic storage medium
WO2019049585A1
